Phosphorus removal from water with an iron functionalised biochar produced from sunflower seed husks: A circular economy-based solution for the agro sector - Sanja Cojbasic; Sabolc Pap; Jelena Prodanovic; John Milan van der Bergh; Stuart W. Gibb; Ulrike Gayh; Maja Turk Sekulic (Biomass and Bioenergy, 2026)

Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Six weeks of isometric resistance training led to evidence of corticospinal but not reticulospinal adaptation in previously untrained adult males - Simon Walker; Katherine E. J. Keogh; Meghan Tanel; Aidan S. W. Baker; Anne M. E. Baker; Dawson J. Kidgell; Stuart N. Baker (Experimental Brain Research, 2026)
The latest hypothesis regarding the source of enhanced neural activation from resistance training is the reticulospinal rather than the corticospinal tract, based on invasive animal and emerging human data. The present study employed a six-week isometric resistance training intervention in a randomized controlled design to address this knowledge gap. Thirty-nine healthy, untrained males (age ~23 y, sustained contraction group n = 13, explosive contraction group n = 9, control group n = 17) underwent neuromuscular and electrophysiological testing and completed all study requirements. Maximal isometric torque (MVC) and rate of torque development (RTD) were measured during a familiarization session as well as before and after the six-week period. Transcranial magnetic stimulation was used to assess motor-evoked potential (MEP) area and silent period duration while subjects contracted to 10% of MVC. Loud sound (120 dB) was used to modulate MEP area and reaction time to visual stimuli during the StartReact test. Only the intervention groups demonstrated significant improvements in MVC (27%) and RTD (60%) (both P < 0.01), along with reduced MEP area (− 21%) and silent period duration (− 23%) (both P < 0.01). The sustained contraction group showed reduced modulation of reaction time and increased MEP suppression due to loud sound. Short-term resistance training seemed to reduce cortical inhibition and corticospinal excitability in both training groups. The study showed conflicting changes in measures purported to evaluate reticulospinal functioning. It is recommended to examine different forms of resistance training and longer training exposure in future.

Pan-continental assessment of socioeconomic and environmental predictors of PFAS occurrence in European rivers from a harmonised monitoring study - Jun Li; Alistair B.A. Boxall; Caroline Swan; Selwyn Hoeks; Racliffe W.S. Lai; John L. Wilkinson; Recep C. Altinbag; Åsa Arrhenius; Roman Ashauer; Thomas Backhaus; Besnik Baraj; Vasiliki G. Beretsou; et al. (Water Research, 2026)

Integrated geological, economic, and risk assessment of underground hydrogen storage - Prakash Purswani; K C Bijay; Hyeonseok Lee; Yun Yang; Uwaila C. Iyare; Lawrence O. Baompong; Shaowen Mao; David Z. Li; Zhidi Wu; Manjeet Chhetri; Siqin Yu; Xiaoyu Zhang; et al. (Fuel, 2026)

Intact coastal nursery rearing amid climate‐driven phenological shifts in threatened salmon - Stuart H. Munsch; Joseph H. Anderson; Eric M. Beamer; Joshua W. Chamberlin; Christopher Ellings; Correigh M. Greene; Sayre Hodgson; Michael T. LeMoine; W. Todd Zackey (Conservation Biology, 2026)
Literature linking phenology to climate has proliferated in recent decades and shows that climate change has reorganized seasonal opportunities worldwide. However, this literature often quantifies changes in point measures of timing (e.g., beginnings and peaks) without context about duration (e.g., rearing season length) or performance (e.g., juvenile development). Consequently, phenological studies often cannot discern whether climate change truncates biological processes or merely recenters them intact around different dates, which limits the utility of these studies for climate vulnerability assessments. Showing how research may bridge this gap, we quantified links between temperature and coastal nursery rearing phenology in threatened Chinook salmon ( Oncorhynchus tshawytscha , Walbaum 1792). Long nursery rearing periods are crucial to enabling growth that promotes survival and life‐history diversity that spreads risk. Because salmon can express diverse, climate‐influenced phenologies and our study region warmed but remained temperate, we sought to discern whether nursery rearing was intact or truncated amid potential phenological change. Leveraging ∼170,000 observations across three decades and three basins, we found that warm years generally advanced populations’ seasonal trajectories of habitat use and growth and that they did not reduce annual 95th percentile body lengths. Additionally, warm years did not consistently compress or expand habitat use in rivers or deltas but consistently expanded habitat use in nearshore marine waters. Overall, there was substantial evidence that warm years advanced nursery rearing intact and little evidence of truncation. Thus, climate change shifted when populations reared but did not prevent populations from completing rearing. Global research on phenological change has begun to transcend descriptions of patterns to consider biological consequences. Simultaneously, efforts to assess populations’ climate vulnerabilities have become widespread. Studies that inspect phenological change to distinguish intact processes from truncated processes could provide insights into climate vulnerabilities. Coastal nursery rearing is one process that may especially befit this framework.

Effect of six weeks ubiquinol supplementation on mitochondrial respiratory function and exercise capacity in healthy males - Jarred P. Acton; Nehal S. Alsharif; Jack W. Bond; Stuart P. Cocksedge; Abbie G. Mclellan; Donald L. Peden; Mark P. Funnell; Hannah F. Dugdale; Lewis J. James; Richard A. Ferguson; Tom Clifford; Stephen J. Bailey (European Journal of Applied Physiology, 2026)
Coenzyme Q10 (CoQ 10 ) is an integral component of the mitochondrial electron transfer system. Most studies have administered the oxidised form of CoQ 10 (ubiquinone) and observed no effects on mitochondrial respiratory function or endurance exercise performance. The reduced form of CoQ 10 , ubiquinol (UQH 2 ), has greater bioavailability than ubiquinone, but the effects of UQH 2 supplementation on mitochondrial respiratory function and exercise capacity are unclear. Fifty-four healthy, recreationally active males were randomised to receive either 300 mg·day − 1 UQH 2 or placebo (PLA) for 6 weeks in a double-blind independent-group design. Before and after the supplementation period, skeletal muscle mitochondrial respiration variables and protein content of the mitochondrial leak proteins, adenine nucleotide translocase1 + 2 (ANT1 + 2) and uncoupling protein-3 (UCP-3), were assessed. In addition, participants completed a severe-intensity cycle test to exhaustion to assess time to the limit of tolerance (T Lim ) and oxygen uptake (V̇O 2 ) kinetics. Compared to pre-supplementation and PLA, UQH 2 supplementation increased plasma [CoQ 10 ] ( P < 0.05), and lowered inverse respiratory control ratio (Pre-PLA: 0.064 ± 0.034 vs. Post-PLA: 0.072 ± 0.026; Pre- UQH 2 : 0.073 ± 0.039 vs. Post-UQH 2 : 0.044 ± 0.019; P < 0.05), suggestive of improved oxidative phosphorylation coupling efficiency. There were no differences in ANT1 + 2 or UCP-3 protein content post-supplementation compared to pre-supplementation between groups ( P > 0.05). End-exercise V̇O 2 , change in V̇O 2 between 2 min and end-exercise, and T Lim were not different between groups post-supplementation ( P > 0.05). Six-weeks UQH 2 supplementation increased plasma [CoQ 10 ] and oxidative phosphorylation coupling efficiency, but did not alter mitochondrial leak proteins, T Lim or V̇O 2 kinetics during severe-intensity exercise in healthy, active males.

Bayesian hierarchical stock–recruitment models for setting conservation limits for Atlantic salmon stocks in Scotland - James P. Ounsley; Nora N. Hanson; Gordon W. Smith; Jonathan P. Gillson; Brian A. Shields; Stuart J. Middlemas (Journal of Fish Biology, 2026)
Atlantic salmon ( Salmo salar L.) populations in Scotland are subject to active management and conservation practices which require biological reference points (BRPs), specifically conservation limits, defined at the level of the stock. Acquiring the data necessary to independently derive these BRPs for all managed populations in Scotland is prohibitive, motivating the use of Bayesian hierarchical stock–recruitment models. These models provide a framework for the joint analysis of multiple monitored stocks, and the transportation of BRPs to non‐monitored stocks. This framework was adapted to introduce nationally relevant and available covariates that might explain variation in recruitment dynamics among stocks and reduce uncertainty in posterior predictions of BRPs. Model selection was designed to maximise the prediction of BRPs for new stocks via leave‐one‐group‐out cross‐validation. Out‐of‐sample predictive performance was maximised by including information on latitude, land usage within the catchment and historic catch per area of salmon habitat in the model. The extensions to Bayesian hierarchical stock–recruitment methods presented here, when applied at a national scale, result in more locally discriminative posterior predictions compared to existing methods and are readily applicable to other stocks and species.

The future of evolutionary behavioral biology - Theo C. M. Bakker; James F. A. Traniello; Tim R. Birkhead; Monika Borgerhoff Mulder; Bernard Crespi; Niels J. Dingemanse; Raghavendra Gadagkar; Ashleigh S. Griffin; Mark E. Hauber; Bert Hölldobler; John L. Hoogland; Sarah B. Hrdy; et al. (Behavioral Ecology and Sociobiology, 2026)

Correction to: The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2026)

Mapping area of habitat for inland wetland species - Francesca A. Ridley; Catherine A. Sayer; Louise Mair; Daniele Baisero; Monika Böhm; Thomas M. Brooks; Stuart H. M. Butchart; Viola Clausnitzer; Jeorg Freyhof; Günther Grill; Ian Harrison; Randall R. Jiménez; et al. (Conservation Biology, 2026)
Area of habitat (AOH) maps provide a high‐resolution representation of the habitat available in a species’ range and can support conservation policy and planning processes. However, until recently, there was insufficient knowledge on the distribution of inland wetlands and freshwater biodiversity to develop AOH mapping methods specifically tailored to inland wetlands. We used a combined empirical and thematic approach to translate inland wetland habitat classes in the International Union for Conservation of Nature (IUCN) Habitats Classification Scheme into spatially explicit wetland‐cover types derived from the Global Lakes and Wetlands Database 2 and the World Karst Aquifer Map. The AOH was subsequently estimated as the area in the mapped range that corresponded to each species’ habitat and elevation associations. We developed and tested the method with IUCN Red List assessment data, range maps, and point locality data for fishes, odonates, decapod crustaceans, and mollusks (22,876 species). The method performed well in comparison with similar methods already developed for terrestrial mammals, birds, amphibians, and reptiles. The mean map prevalence (proportion of area in a species’ range that was AOH) was 18–32% for each taxonomic group. Based on data on known localities of occurrence, 78–100% of species per taxonomic group had a higher classification accuracy than expected if AOH were distributed in the range at random. This represents an increased accuracy in the distribution of wetland species. Our study represents the first attempt to distinguish between inland wetland habitat subclasses and to include subterranean habitats in an AOH mapping method. Our method will facilitate the inclusion of previously underrepresented taxa in key conservation tools and analyses and is expected to increase the accuracy of AOH mapping for any species associated with inland wetlands.

A horizon scan of biological conservation issues for 2026 - William J. Sutherland; Stuart H.M. Butchart; Stewart J. Clarke; Nigel R. Doar; Helen Doran; Imogen C. Douglas; Daniel J. Field; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Hermanni Kaartokallio; et al. (Trends in Ecology & Evolution, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Missing or Mis‐Telling the Story? Trade‐Offs for Restriction‐Site Associated Compared to Whole Genome Sequencing - Kamolphat Atsawawaranunt; Katarina C. Stuart; Annabel Whibley; Kyle M. Ewart; Lee A. Rollins; Rebecca N. Johnson; Anna W. Santure (Molecular Ecology, 2026)
Researchers must navigate several trade‐offs when deciding which population sequencing method to use. The decision between reduced representation approaches and whole genome sequencing (WGS) impacts marker density, sequencing depth and costs per sample, which will in turn affect the power to accurately characterise certain genomic features, such as regions of the genome exhibiting signals of selection. To investigate the effect of sequencing method on the detection of putatively adaptive regions, we compared selection scan analyses of a set of restriction site‐associated DNA sequencing (RADseq) datasets for the common myna ( Acridotheres tristis ) with a WGS dataset with fewer individuals. Although selection scan statistics were found to be correlated between datasets, no common outliers were found when using outlier thresholds typically applied in such studies. We compared allele frequencies and genotypes across datasets and found that discordances were due to missing markers, different individuals sampled or erroneous genotyping. Most importantly, two regions with strong signals of selection identified through WGS data were missed in the lower density dataset, and population‐specific allelic dropout, which can result from restriction enzyme cut site loss in RADseq, created false signals of selection in these datasets. Our results highlight the advantages of WGS over RADseq when used for selection scan analyses, especially for highly structured populations such as those observed in many invasive or endangered species.

Removal of Copper and Lead Ions from Water Using Dopamine-Modified Waste Marine Plastic - Huiyi Zhang; Stuart W. Gibb; Neil A. James; Kenneth G. Boyd; Sabolc Pap (Environmental Processes, 2025)

Both Structural Variant and Single Nucleotide Polymorphism Load Impact Lifetime Fitness in a Threatened Bird Species - Katarina C. Stuart; Hui Zhen Tan; Annabel Whibley; Sarah Bailey; Patricia Brekke; John G. Ewen; Selina Patel; Anna W. Santure (Molecular Ecology, 2025)
The field of conservation genomics is becoming increasingly interested in whether, and how, structural variant (SV) genotype information can be leveraged in the management of threatened species. The functional consequences of SVs are more complex than for single nucleotide polymorphisms (SNPs), as SVs typically impact a larger proportion of the genome due to their size and thus may be more likely to contribute to load. While the impacts of SV‐specific genetic load may be less consequential for large populations, the interplay between weakened selection and stochastic processes means that smaller populations, such as those of the threatened Aotearoa hihi/New Zealand stitchbird ( Notiomystis cincta ), may harbour a high SV load. Hihi were once confined to a single remnant population, but have been reestablished into six sanctuaries and reserves, often via secondary bottlenecks, resulting in low genetic diversity, low adaptive potential, and inbreeding depression. In this study, we use whole genome resequencing of 30 individuals from the Tiritiri Matangi population to identify the nature and distribution of both SNPs and SVs within this small avian population. We find that SNP and SV individual mutation load is only moderately correlated, likely because SVs arise in regions of high recombination and that are less evolutionarily conserved. Finally, we leverage a long‐term monitoring dataset of pedigree and fitness data to assess the impact of SNP and SV mutation loads on individual fitness, and find that SNP and SV realised load had similar negative correlations with lifetime fitness. However, of the masked load metrics, only SVs had a positive significant correlation with lifetime fitness, indicating that masking of deleterious alleles may be more important for SVs than for SNPs. The results of this study indicate that only examining SNPs neglects important aspects of intra‐specific variation and that studying SVs has direct implications for linking genetic diversity and genomic health to inform management decisions.

Acoustic Monitoring Enables Multi‐Taxa Conservation Assessment and Prioritisation Over Large Scales and for Rare and Cryptic Species - Adham Ashton‐Butt; Stuart E. Newson; Jeffrey W. Doser; Simon Gillings; Tatiana Kornienko; Viktar Fenchuk; James W. Pearce‐Higgins; Chris Scott; Philip W. Atkinson (Global Ecology and Biogeography, 2025)
Aim To combat the global biodiversity crisis, robust and scalable data are needed to target, monitor and evaluate conservation efforts, particularly in data‐poor regions and for cryptic taxa. Passive acoustic monitoring (PAM) has the potential to provide solutions, but real‐world examples are still rare. We demonstrate how PAM data can be used to rapidly and effectively map distributions of multiple taxa over large scales, in data‐poor regions. We show how these data can be used to assess the importance of existing protected areas and prioritise future conservation efforts, including for rare and cryptic species often neglected in such assessments. Location Global with a case study from Polesia, Eastern Europe. Time Period Present. Major Taxa Studied Bats, Birds, Small mammals and Bush crickets. Methods Using machine‐learning and manual verification, we identified bats, nocturnally active birds, small mammals and bush crickets from over 34,000 monitoring hours at 506 sites in the Polesia region of Belarus and Ukraine. Using multi‐species generalised mixed models in a Bayesian framework, we then predicted occupancy and acoustic activity for these species and their associations with protected areas, over a 151,000 km 2 project area. We identified areas of high conservation priority as measured by species richness and/or importance for globally or regionally threatened species. Main Conclusions Our approach provides a roadmap for collecting and processing large‐scale, multi‐taxa biodiversity data using passive acoustic monitoring. In our case study region, we show that although existing protected areas contain a relatively large proportion of high conservation priority areas, there are significant gaps in the protected area network. We also show low surrogacy of areas of high conservation priority between taxa at fine scales, but did at larger scales, showing the importance of multi‐taxa monitoring to prioritise protected areas that conserve a wide variety of species.

A plea for scientific integrity: a comment on the honeybee odometer controversy - Geoffrey W. Stuart (Journal of Comparative Physiology A, 2025)

Hindsight informs foresight: revisiting millennial forecasts of impacts and status of rocky shores in 2025 - Stephen J. Hawkins; Kathryn A. O'Shaughnessy; George M. Branch; Laura Airoldi; Simon Bray; Paul Brooks; Michael T. Burrows; Juan Carlos Castilla; Tasman P. Crowe; Thomas W. Davies; Louise B. Firth; Keith Hiscock; et al. (Marine Pollution Bulletin, 2025)

Population Genetics and Invasion History of the European Starling Across Aotearoa New Zealand - Bryan Thompson; Kamolphat Atsawawaranunt; Melissa C. Nehmens; William S. Pearman; E. Owen Perkins; Pavel Pipek; Lee A. Rollins; Hui Zhen Tan; Annabel Whibley; Anna W. Santure; Katarina C. Stuart (Molecular Ecology, 2025)
The expansion of human settlements over the past few centuries is responsible for an unprecedented number of invasive species introductions globally. An important component of biological invasion management is understanding how introduction history and postintroduction processes have jointly shaped present‐day distributions and patterns of population structure, diversity and adaptation. One example of a successful invader is the European starling ( Sturnus vulgaris ), which was intentionally introduced to numerous countries in the 19th century, including Aotearoa New Zealand, where it has become firmly established. We used reduced representation sequencing to characterise the genetic population structure of the European starling in New Zealand, comparing it to that present in sampling locations in the native range and invasive Australian range. The population structure and genetic diversity patterns we found suggested restricted gene flow from the majority of New Zealand to the northmost sampling location (Auckland). We also profiled genetic bottlenecks and shared outlier genomic regions, which supported historical accounts of translocations between both Australian subpopulations and New Zealand, and provided evidence of which documented translocation events were more likely to have been successful. Using these results as well as historic demographic patterns, we demonstrate how genomic analysis complements even well‐documented invasion histories to better understand invasion processes, with direct implications for understanding contemporary gene flow and informing invasion management.

The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2025)

Estimating estuary habitat change and functional trajectory of restoration projects over two decades in Puget Sound, WA - Joshua W. Chamberlin; Oleksandr Stefankiv; Eric M. Beamer; Correigh M. Greene; W. Gregory Hood; Stuart H. Munsch (Frontiers in Marine Science, 2025)
Estuaries provide many important functions for numerous aquatic species across life stages. However, these habitats have been widely impacted due to their characteristics and features that support agriculture and industrialization. Within Puget Sound, estuary restoration has been a primary tool to support recovery of Chinook salmon which are known to rely heavily on estuaries during early life history. Tracking habitat gains via restoration and evaluating effectiveness of these actions is necessary to ensure recovery targets are met. We used aerial imagery from two distinct time periods to measure estuarine habitat and estimate rates of change over two decades in Puget Sound. In addition, we developed a method to estimate functional trajectories for restoration projects based on allometry of planform geometry features for tidal deltas. A total of 72 restoration actions across nine tidal deltas added ~147 ha and ~410 km of tidal channel habitat in Puget Sound between 1997 and 2018. While positive overall, time series of rearing habitat change for individual tidal deltas varied reflecting the frequency and magnitude of restoration actions as well as the response of individual actions to natural processes. Estimated functional footprints for restoration projects were below total footprints for all deltas. Functional footprints appeared to track total footprint well for some deltas but indicated potential limitations in others that may be related to particular planform geometry metrics for individual sites. Overall restoration of estuarine habitats in Puget Sound since 1997 have added substantial rearing habitat in support of recovery for Chinook salmon populations. While total gains are positive, our estimates of functional trajectories provide additional information that may support adaptive management to ensure efforts remain beneficial to target species. Continuing to accurately track changes to estuarine habitat should benefit recovery efforts and support management decisions in the future.

Concurrent invasions of European starlings in Australia and North America reveal population‐specific differentiation in shared genomic regions - Natalie R. Hofmeister; Katarina C. Stuart; Wesley C. Warren; Scott J. Werner; Melissa Bateson; Gregory F. Ball; Katherine L. Buchanan; David W. Burt; Adam P. A. Cardilini; Phillip Cassey; Tim De Meyer; Julia George; et al. (Molecular Ecology, 2025)
A species' success during the invasion of new areas hinges on an interplay between the demographic processes common to invasions and the specific ecological context of the novel environment. Evolutionary genetic studies of invasive species can investigate how genetic bottlenecks and ecological conditions shape genetic variation in invasions, and our study pairs two invasive populations that are hypothesized to be from the same source population to compare how each population evolved during and after introduction. Invasive European starlings ( Sturnus vulgaris ) established populations in both Australia and North America in the 19th century. Here, we compare whole‐genome sequences among native and independently introduced European starling populations to determine how demographic processes interact with rapid evolution to generate similar genetic patterns in these recent and replicated invasions. Demographic models indicate that both invasive populations experienced genetic bottlenecks as expected based on invasion history, and we find that specific genomic regions have differentiated even on this short evolutionary timescale. Despite genetic bottlenecks, we suggest that genetic drift alone cannot explain differentiation in at least two of these regions. The demographic boom intrinsic to many invasions as well as potential inversions may have led to high population‐specific differentiation, although the patterns of genetic variation are also consistent with the hypothesis that this infamous and highly mobile invader adapted to novel selection (e.g., extrinsic factors). We use targeted sampling of replicated invasions to identify and evaluate support for multiple, interacting evolutionary mechanisms that lead to differentiation during the invasion process.

Population responses of Chinook salmon to two decades of restoration of estuary nursery habitat - Correigh M. Greene; Eric M. Beamer; Stuart H. Munsch; Joshua W. Chamberlin; Michael T. LeMoine; Joseph H. Anderson (Frontiers in Marine Science, 2025)
Estuaries comprise important but often-degraded fish nursery habitat. People have invested considerable resources into restoring estuaries to rehabilitate habitats, but comparatively little work has evaluated population outcomes for target species. Here, we examined the response of a threatened population of Chinook salmon ( Oncorhynchus tshawytscha ) to estuary restoration in their natal tidal delta, and observed demographic changes consistent with increasing nursery habitat capacity and quality. We leveraged three decades of monitoring before, during, and after restoration in the Skagit River delta, and compared demographic patterns in restored and unrestored forks within the delta, and in locations landward and seaward of the delta. We hypothesized that restoration in tidal deltas should result in reductions in local densities, and reduced density-dependent spillover of juveniles into nearshore waters. We also examined other predictions that were more ambiguous and depended upon biological mechanisms. We found that (1) delta restoration led to lower juvenile densities overall and greater juvenile densities when conspecific abundances were high, and (2) individual juveniles were smaller overall and their lengths declined less when densities were higher. We also monitored juvenile salmon in nearshore waters seaward of the delta. Following delta restoration, (3) juvenile catches in nearshore marine waters declined relative to delta habitat change, and (4) the prevalence of nearshore fry (<~45 mm) — a phase thought to benefit more from delta nursery habitats — decreased overall. These findings suggest that greater nursery habitat capacity in the delta allowed salmon to spread out and accommodated higher salmon numbers when juvenile outmigrations were especially high. They also suggest that restoration promoted the use of delta habitats by smaller fish while alleviating competitive effects on growth. Furthermore, they suggest that greater delta habitat capacity supported more juveniles, decreasing overflow to nearshore environments, especially for the smallest, most vulnerable salmon that presumably benefit most from growth before entering nearshore waters. Thus, estuary restoration appeared to alleviate density-dependent constraints on rearing and growth. These findings provide empirical support for restoring estuaries in human-stressed landscapes to rehabilitate nursery habitat functions for Chinook salmon and, potentially, other species and life stages.

Correction to: Biogeophysical drivers of abundance for habitat-shifting reef fishes on stepping-stone coral patch reefs - Sofia W. S. Panzetta; Courtney E. Stuart; Stephanie J. Green (Coral Reefs, 2025)

Biogeophysical drivers of abundance for habitat-shifting reef fishes on stepping-stone coral patch reefs - Sofia W. S. Panzetta; Courtney E. Stuart; Stephanie J. Green (Coral Reefs, 2025)

Isolation and characterisation of two epithelial-like cell lines from the gills of Chrysophrys auratus (Australasian snapper) and Oncorhynchus tshawytscha (Chinook salmon) and their use in aquatic toxicology - Björn Böhmert; Gavril L. W. Chong; Kim Lo; Michael Algie; Damon Colbert; Melissa D. Jordan; Gabriella Stuart; Lyn M. Wise; Lucy E. J. Lee; Niels C. Bols; Georgina C. Dowd (In Vitro Cellular & Developmental Biology - Animal, 2025)
In vitro gill models are becoming increasingly important in aquatic toxicology, yet the fish gill invitrome is underrepresented, encompassing approximately 0.1% of extant species. Here, we describe the establishment and characterisation of two gill-derived, epithelial-like cell lines isolated from fish species of significant importance to New Zealand: Chrysophrys auratus (Australasian snapper) and Oncorhynchus tshawytscha (Chinook salmon). Designated CAgill1PFR ( Chrysophrys auratus, gill 1 , P lant & F ood R esearch) and OTgill1PFR ( Oncorhynchus tshawytscha, gill 1 , P lant & F ood R esearch), these cell lines have each been passaged greater than each 70 times over several years and are considered spontaneously immortalised. Both cell lines required serum for growth and exhibited differential responses to basal media formulations. CAgill1PFR was sensitive to low temperatures (4 °C) but replicated at high temperatures (30 °C), whereas OTgill1PFR was sensitive to high temperatures but remained viable at low temperatures, mirroring the natural environment of their host species. Immunostaining revealed expression of epithelial cell markers cytokeratin and E-cadherin, alongside positivity for the mesenchymal cell marker, vimentin. CAgill1PFR was more sensitive to the environmental toxin 3,4 dichloroaniline than OTgill1PFR through measurements of metabolic activity, membrane integrity, and lysosomal function. Furthermore, CAgill1PFR produced less CYP1A activity, indicative of ongoing biotransformation processes, in response to beta-naphthoflavone than OTgill1PFR. These cell lines expand the toolbox of resources and emphasise the need for species-specific aquatic toxicology research.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Supplementation strategies to control propionic acid accumulation resulting from ammonia inhibition in dry anaerobic digestion: Osmoprotectants, activated carbon and trace elements - Ildefonso Rocamora; Stuart T. Wagland; Francis Hassard; Raffaella Villa; Miriam Peces; Ioannis A. Fotidis; Edmon W. Simpson; Oliver Fernández; Yadira Bajón-Fernández (Journal of Environmental Chemical Engineering, 2025)

Marine snow as vectors for microplastic transport: Multiple aggregation cycles account for the settling of buoyant microplastics to deep‐sea sediments - Nan Wu; Stuart W. D. Grieve; Andrew J. Manning; Kate L. Spencer (Limnology and Oceanography, 2025)
Many studies have reported the paradoxical observation of high concentrations of low‐density microplastics (plastic particles μ m in diameter can reach the ocean bottom. This theoretical model refines our ability to predict and understand the global and long‐term fate, transport, and inventory of microplastics in the ocean interior, the influence of microplastics on the biological carbon pump and the efficacy of plastic management policies.

Sustainable remediation of macrolide antibiotic from water using a novel Fe oxide/biochar nanocomposite: Adsorption behaviour and mechanistic analysis - Sabolc Pap; Lisa Shearer; Stuart W. Gibb (Journal of Environmental Chemical Engineering, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

The emerging role of alternatively activated macrophages to treat acute liver injury - Chris Humphries; Melisande L. Addison; James W. Dear; Stuart J. Forbes (Archives of Toxicology, 2025)
Acute liver injury (ALI) has a clear requirement for novel therapies. One emerging option is the use of alternatively activated macrophages (AAMs); a distinct subtype of macrophage with a role in liver injury control and repair. In this comprehensive review, we provide an overview of the current limited options for ALI, and the potential advantages offered by AAMs. We describe the evidence supporting their use from in vitro studies, pre-clinical animal studies, and human clinical trials. We suggest why the first evidence for the clinical use of AAMs is likely to be found in acetaminophen toxicity, and discuss the specific evidence for AAM use in this population, as well as potential applications for AAMs in other patient populations. The key domains by which the performance of AAMs for the treatment of ALI will be assessed are identified, and remaining challenges to the successful delivery of AAMs to clinic are explored.

Parallel Signatures of Diet Adaptation in the Invasive Common Myna Genome - Kamolphat Atsawawaranunt; Katarina C. Stuart; Annabel Whibley; Kyle M. Ewart; Richard E. Major; Rebecca N. Johnson; Anna W. Santure (Molecular Ecology, 2025)
Invasive species offer uniquely replicated model systems to study rapid adaptation. The common myna ( Acridotheres tristis ) has been introduced to over a dozen countries and is classified as one of the most invasive birds in the world. Their multiple invasions provide an opportunity to identify repeated adaptation, as invasive populations originated from multiple source populations. We compared whole‐genome resequencing data from 80 individuals from four native and seven invasive populations, representing two independent introduction pathways. Results from two different selection scan methods were combined and identified a strongly selected region on chromosome 8 that spans two copies of AMY2A, part of the alpha‐amylase gene family, a putative ncRNA and an insertion–deletion structural variant (SV) that contains an ERVK transposable element (TE). Outlier SNPs and the SV are polymorphic in native populations, but fixed or close‐to‐fixed in the two invasive pathways, with the fixation of the same alleles in two independent lineages providing evidence for parallel selection on standing variation. Intriguingly, the second copy of AMY2A has a non‐conservative missense mutation at a phylogenetically conserved site. This mutation, alongside variation in the SV, TE and ncRNA, provide possible routes for changes to protein function or expression. AMY2A has been associated with human commensalism in house sparrows, and genes in this family have been linked to adaptation to high‐starch diets in humans and dogs. This study illustrates the value of replicated analyses within and across species to understand rapid adaptation at the molecular level.

Evaluation of ballistics euthanasia applied to stranded cetaceans using ethological and post-mortem computed tomography assessment - Rebecca M. Boys; Brian C. W. Kot; Gordon Lye; Ngaio J. Beausoleil; Stuart Hunter; Karen A. Stockin (Veterinary Research Communications, 2024)
Debilitated stranded cetaceans with low survival likelihood, may require euthanasia to avoid further suffering. Euthanasia can involve chemical or physical methods, including ballistics. Ballistics should cause instantaneous, permanent insensibility through brainstem disruption. Despite wide application, there is limited understanding of ballistics-related welfare outcomes. We opportunistically examined behaviour of three maternally-dependent cetaceans following shooting and the related cranial disruption post-mortem using computed tomography (PMCT). Our aim was to understand whether a ‘humane death’, i.e., euthanasia, was achieved. Each animal was shot using different projectile types: soft non-bonded, solid, and soft bonded. In two animals, insensibility was not immediately assessed following shooting, although both were reported as ‘instantaneously insensible’. From our analysis, all animals displayed musculoskeletal responses to shooting, including peduncle stiffening and slack lower jaw, followed by musculature relaxation 24-, 10.3- and 20.8-seconds post-ballistics, respectively. The animal shot with a soft non-bonded projectile also displayed agonal convulsions and tail-lifting for 16-seconds post-shot; these were not observed for solid or soft bonded projectiles. PMCT findings indicated projectile disruption to the brainstem and/or spinal cord likely to cause near-instantaneous insensibility. However, extra-cranial wounding was also evident for the soft non-bonded projectile, highlighting potential for additional welfare compromise. Our results demonstrate that ballistics can achieve a relatively rapid death in young, stranded cetaceans, but careful equipment selection is required. To ensure a humane death, verification of insensibility must be undertaken immediately following shooting. Further studies should be undertaken to improve knowledge of appropriate procedures and equipment for euthanasia, ensuring humane deaths for compromised cetaceans.

Nutrients and polyphenols-rich Sorghum bicolor genotypes as complementary therapy for Alzheimer’s disease - Rasheed A. Abdulraheem; Ralph N. Martins; Prashant Bharadwaj; Zhaoyu Li; Ranil Coorey; Stuart Johnson; W. M. A. D. Binosha Fernando (Phytochemistry Reviews, 2024)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder and most common cause of dementia among older people. The main pathological hallmarks of AD are formation of insoluble amyloid beta senile plaques and paired helical filaments of neurofibrillary tangles. AD features gradual memory decline, mild to severe cognitive impairment, eventually total dependence of patients on caregivers. Currently available drugs have not been able to modify AD pathology. This has drawn increasing attention to plant food materials with high nutritional and bioactive constituents as potential complementary therapy for AD. Sorghum bicolor is a widely available cost-effective source of proteins, fats, crude fibres, biopeptides and polyphenols which are vital for human wellbeing. This review discussed the major mechanisms underlying AD pathology. The nutritional and bioactive constituents of Sorghum bicolor grains were extensively described. There is limited report on anti-AD activities of sorghum grains. Therefore, the pharmacological mechanisms of action including scavenging of reactive oxygen species, inhibition of oxidative stress, anti-acetylcholinesterase activity and modulation of mitophagy were only speculated. This comprehensive update suggests more robust innovative studies that will provide critical theoretical details necessary to promote utilization of sorghum grains as functional food or source of bioactive molecules for AD therapy.

Evaluating rational and healthy use options for small pelagic fish species in sub-Saharan Africa - Stuart W. Bunting; Djiga Thiao; Molly Ahern; Yaw B. Ansah; Ansen Ward; Joshua Wesana; Rodrigue Yossa; Lena Westlund (Food Security, 2024)

Associations between MASLD, atrial fibrillation, cardiovascular events, mortality and aspirin use in older adults - Daniel Clayton-Chubb; Stuart K. Roberts; Ammar Majeed; Robyn L. Woods; Andrew M. Tonkin; Mark R. Nelson; Andrew T. Chan; Joanne Ryan; Cammie Tran; Alexander Hodge; John S. Lubel; Hans G. Schneider; et al. (GeroScience, 2024)

Properties of outer solar system pebbles during planetesimal formation from meteor observations - Peter Jenniskens; Paul R. Estrada; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; et al. (Icarus, 2024)

Exome variant prioritization in a large cohort of hearing-impaired individuals indicates IKZF2 to be associated with non-syndromic hearing loss and guides future research of unsolved cases - Hedwig M. Velde; Maryam Vaseghi-Shanjani; Jeroen J. Smits; Gayatri Ramakrishnan; Jaap Oostrik; Mieke Wesdorp; Galuh Astuti; Helger G. Yntema; Lies Hoefsloot; Cris P. Lanting; Martijn A. Huynen; Anna Lehman; et al. (Human Genetics, 2024)
Although more than 140 genes have been associated with non-syndromic hereditary hearing loss (HL), at least half of the cases remain unexplained in medical genetic testing. One reason is that pathogenic variants are located in ‘novel’ deafness genes. A variant prioritization approach was used to identify novel (candidate) genes for HL. Exome-wide sequencing data were assessed for subjects with presumed hereditary HL that remained unexplained in medical genetic testing by gene-panel analysis. Cases in group AD had presumed autosomal dominantly inherited HL (n = 124), and in group AR, presumed autosomal recessive HL (n = 337). Variants in known and candidate deafness genes were prioritized based on allele frequencies and predicted effects. Selected variants were tested for their co-segregation with HL. Two cases were solved by variants in recently identified deafness genes ( ABHD12 , TRRAP ). Variant prioritization also revealed potentially causative variants in candidate genes associated with recessive and X-linked HL. Importantly, missense variants in IKZF2 were found to co-segregate with dominantly inherited non-syndromic HL in three families. These variants specifically affected Zn 2+ -coordinating cysteine or histidine residues of the zinc finger motifs 2 and 3 of the encoded protein Helios. This finding indicates a complex genotype–phenotype correlation for IKZF2 defects, as this gene was previously associated with non-syndromic dysfunction of the immune system and ICHAD syndrome, including HL. The designed strategy for variant prioritization revealed that IKZF2 variants can underlie non-syndromic HL. The large number of candidate genes for HL and variants therein stress the importance of inclusion of family members for variant prioritization.

Modernizing the US National Fire Danger Rating System (version 4): Simplified fuel models and improved live and dead fuel moisture calculations - W. Matt Jolly; Patrick H. Freeborn; Larry S. Bradshaw; Jon Wallace; Stuart Brittain (Environmental Modelling & Software, 2024)

A framework for optimising opportunistic collaborative syntheses to propel ecological conservation - Ana M.M. Sequeira; Amanda E. Bates; Graeme Hays; David W. Sims; Samantha Andrzejaczek; Asta Audzijonyte; Julia K. Baum; Martin Beal; Barbara Block; Joshua Cinner; Kaitlyn Cowley; Eric Gilman; et al. (Biological Conservation, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Artificial light and cloud cover interact to disrupt celestial migrations at night - Leo M. Burke; Thomas W. Davies; David Wilcockson; Stuart Jenkins; Amy Ellison (Science of The Total Environment, 2024)

Methane fluxes in tidal marshes of the conterminous United States - Ariane Arias‐Ortiz; Jaxine Wolfe; Scott D. Bridgham; Sara Knox; Gavin McNicol; Brian A. Needelman; Julie Shahan; Ellen J. Stuart‐Haëntjens; Lisamarie Windham‐Myers; Patty Y. Oikawa; Dennis D. Baldocchi; Joshua S. Caplan; et al. (Global Change Biology, 2024)
Methane (CH 4 ) is a potent greenhouse gas (GHG) with atmospheric concentrations that have nearly tripled since pre‐industrial times. Wetlands account for a large share of global CH 4 emissions, yet the magnitude and factors controlling CH 4 fluxes in tidal wetlands remain uncertain. We synthesized CH 4 flux data from 100 chamber and 9 eddy covariance (EC) sites across tidal marshes in the conterminous United States to assess controlling factors and improve predictions of CH 4 emissions. This effort included creating an open‐source database of chamber‐based GHG fluxes ( https://doi.org/10.25573/serc.14227085 ). Annual fluxes across chamber and EC sites averaged 26 ± 53 g CH 4 m −2 year −1 , with a median of 3.9 g CH 4 m −2 year −1 , and only 25% of sites exceeding 18 g CH 4 m −2 year −1 . The highest fluxes were observed at fresh‐oligohaline sites with daily maximum temperature normals (MATmax) above 25.6°C. These were followed by frequently inundated low and mid‐fresh‐oligohaline marshes with MATmax ≤25.6°C, and mesohaline sites with MATmax >19°C. Quantile regressions of paired chamber CH 4 flux and porewater biogeochemistry revealed that the 90th percentile of fluxes fell below 5 ± 3 nmol m −2 s −1 at sulfate concentrations >4.7 ± 0.6 mM, porewater salinity >21 ± 2 psu, or surface water salinity >15 ± 3 psu. Across sites, salinity was the dominant predictor of annual CH 4 fluxes, while within sites, temperature, gross primary productivity (GPP), and tidal height controlled variability at diel and seasonal scales. At the diel scale, GPP preceded temperature in importance for predicting CH 4 flux changes, while the opposite was observed at the seasonal scale. Water levels influenced the timing and pathway of diel CH 4 fluxes, with pulsed releases of stored CH 4 at low to rising tide. This study provides data and methods to improve tidal marsh CH 4 emission estimates, support blue carbon assessments, and refine national and global GHG inventories.

Lanthanum and cerium functionalised forestry waste biochar for phosphate removal: Mechanisms and real-world applications - Sabolc Pap; Qunying Zhao; Ilgaz Cakin; Paul P.J. Gaffney; Stuart W. Gibb; Mark A. Taggart (Chemical Engineering Journal, 2024)

Limited spatial co-occurrence of wildfire and prescribed burning on moorlands in Scotland - Debbie Fielding; Scott Newey; Robin J. Pakeman; Dave Miller; Zisis Gagkas; Keith Matthews; Stuart W. Smith (Biological Conservation, 2024)

Comparison of two carbonaceous supported Fe-rich adsorbents for arsenate removal: A functionalisation and mechanistic study with applicability to groundwater treatment - Sabolc Pap; Maja Turk Sekulic; Hai Nguyen Tran; Huan-Ping Chao; Peter J. Gilbert; Stuart W. Gibb; Mark A. Taggart (Chemosphere, 2024)

Juvenile survival increases with dispersal distance and varies across years: 15 years of evidence in a prairie perennial - Lea K. Richardson; Scott W. Nordstrom; Amy Waananen; Riley D. Thoen; Amy B. Dykstra; Gretel Kiefer; Drake E. Mullett; Erin G. Eichenberger; Ruth G. Shaw; Stuart Wagenius (Ecology, 2024)
Juvenile survival is critical to population persistence and evolutionary change. However, the survival of juvenile plants from emergence to reproductive maturity is rarely quantified. This is especially true for long‐lived perennials with extended pre‐reproductive periods. Furthermore, studies rarely have the replication necessary to account for variation among populations and cohorts. We estimated juvenile survival and its relationship to population size, density of conspecifics, distance to the maternal plant, age, year, and cohort for Echinacea angustifolia , a long‐lived herbaceous perennial. In 14 remnant prairie populations over seven sampling years, 2007–2013, we identified 886 seedlings. We then monitored these individuals annually until 2021 (8–15 years). Overall, juvenile mortality was very high; for almost all cohorts fewer than 10% of seedlings survived to age 8 or to year 2021. Only two of the seedlings reached reproductive maturity within the study period. Juvenile survival increased with distance from the maternal plant and varied more among the study years than it did by age or cohort. Juvenile survival did not vary with population size or local density of conspecific neighbors. Our results suggest that low juvenile survival could contribute to projected population declines.

Lifetime of cm-sized zodiacal dust from the physical and dynamical evolution of meteoroid streams - Peter Jenniskens; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; Solvay Blomquist; et al. (Icarus, 2024)

Mass spectrometry-based metabolomics for the elucidation of alkaloid biosynthesis and function in invasive Vincetoxicum rossicum populations - Christine J. Kempthorne; Max St. Pierre; Andrew Le; Stuart Livingstone; James McNulty; Marc W. Cadotte; David K. Liscombe (Phytochemistry, 2024)

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

Methane emissions from abandoned oil and gas wells in Colorado - Stuart N. Riddick; Mercy Mbua; Arthur Santos; Ethan W. Emerson; Fancy Cheptonui; Cade Houlihan; Anna L. Hodshire; Abhinav Anand; Wendy Hartzell; Daniel J. Zimmerle (Science of The Total Environment, 2024)

Conservation genomics of the threatened Trispot Darter (Etheostoma trisella) - Kayla M. Fast; Brook L. Fluker; Bernard R. Kuhajda; Patrick E. O’Neil; Stuart W. McGregor; Matthew S. Piteo; Michael W. Sandel (Conservation Genetics, 2024)

On the sensitivity of fire-weather climate projections to empirical fire models - Kevin J. Tory; Miguel G. Cruz; Stuart Matthews; Musa Kilinc; W. Lachlan McCaw (Agricultural and Forest Meteorology, 2024)

Reasons to Be Skeptical about Sentience and Pain in Fishes and Aquatic Invertebrates - Benjamin K. Diggles; Robert Arlinghaus; Howard I. Browman; Steven J. Cooke; Robin L. Cooper; Ian G. Cowx; Charles D. Derby; Stuart W. Derbyshire; Paul JB Hart; Brian Jones; Alexander O. Kasumyan; Brian Key; et al. (Reviews in Fisheries Science & Aquaculture, 2024)

A horizon scan of global biological conservation issues for 2024 - William J. Sutherland; Craig Bennett; Peter N.M. Brotherton; Stuart H.M. Butchart; Holly M. Butterworth; Stewart J. Clarke; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Jennifer James; et al. (Trends in Ecology & Evolution, 2024)

Interrelationships and biogeography of the New World pufferfish genus Sphoeroides (Tetraodontiformes: Tetraodontidae) inferred using ultra-conserved DNA elements - Elizabeth P. Hunt; Stuart C. Willis; Kevin W. Conway; David S. Portnoy (Molecular Phylogenetics and Evolution, 2023)

Effects of management objectives and rules on marine conservation outcomes - Natalie C. Ban; Emily S. Darling; Georgina G. Gurney; Whitney Friedman; Stacy D. Jupiter; W. Peni Lestari; Irfan Yulianto; Sinta Pardede; Sukma A. R. Tarigan; Puji Prihatiningsih; Sangeeta Mangubhai; Waisea Naisilisili; et al. (Conservation Biology, 2023)
Understanding the relative effectiveness and enabling conditions of different area‐based management tools is essential for supporting efforts that achieve positive biodiversity outcomes as area‐based conservation coverage increases to meet newly set international targets. We used data from a coastal social–ecological monitoring program in 6 Indo‐Pacific countries to analyze whether social, ecological, and economic objectives and specific management rules (temporal closures, fishing gear‐specific, species‐specific restrictions) were associated with coral reef fish biomass above sustainable yield levels across different types of area‐based management tools (i.e., comparing those designated as marine protected areas [MPAs] with other types of area‐based management). All categories of objectives, multiple combinations of rules, and all types of area‐based management had some sites that were able to sustain high levels of reef fish biomass—a key measure for coral reef functioning—compared with reference sites with no area‐based management. Yet, the same management types also had sites with low biomass. As governments advance their commitments to the Kunming–Montreal Global Biodiversity Framework and the target to conserve 30% of the planet's land and oceans by 2030, we found that although different types of management can be effective, most of the managed areas in our study regions did not meet criteria for effectiveness. These findings underscore the importance of strong management and governance of managed areas and the need to measure the ecological impact of area‐based management rather than counting areas because of their designation.

In vitro and in vivo accumulation of the anticancer Ru complexes [RuII(cym)(HQ)Cl] and [RuII(cym)(PCA)Cl]Cl - Mie Riisom; Stuart J. Morrow; Caitlin D. Herbert; William D. J. Tremlett; Jonathan W. Astin; Stephen M. F. Jamieson; Christian G. Hartinger (JBIC Journal of Biological Inorganic Chemistry, 2023)

Top ten priorities for global saltmarsh restoration, conservation and ecosystem service research - Julien Pétillon; Emma McKinley; Meghan Alexander; Janine B. Adams; Christine Angelini; Thorsten Balke; John N. Griffin; Tjeerd Bouma; Sally Hacker; Qiang He; Marc J.S. Hensel; Carles Ibáñez; et al. (Science of The Total Environment, 2023)

Beech bark disease does not reduce the long-term wood production of two forests contrasting in age, productivity, and structure - Ellen Stuart-Haëntjens; Jeff W. Atkins; Alexander T. Fotis; Robert T. Fahey; Brady S. Hardiman; Brandon C. Alveshere; Christoph Vogel; Christopher M. Gough (Forest Ecology and Management, 2023)

Knowledge gaps do not preclude extinction risk assessments: A response to Gula et al. (2023) - Alex J. Berryman; Rob W. Martin; Ian J. Burfield; Stuart H.M. Butchart (Biological Conservation, 2023)

Effective rhizobia enhance legume growth during subsequent drought despite water costs associated with nitrogen fixation - Stuart T. Schwab; Kenjiro W. Quides; Camille E. Wendlandt; Jerry Trinh; Matthew Sung; Paola Cardenas; Michael Torres; Louis S. Santiago; Loralee Larios; Joel L. Sachs (Plant and Soil, 2023)

Effective removal of metformin from water using an iron-biochar composite: Mechanistic studies and performance optimisation - Sabolc Pap; Lisa Shearer; Stuart W. Gibb (Journal of Environmental Chemical Engineering, 2023)

Stratification and temporal evolution of mixing regimes in diurnally heated river flows - Cindy Nguyen-Dang; Nicholas Williamson; Steven W. Armfield; Michael P. Kirkpatrick; Stuart E. Norris (Environmental Fluid Mechanics, 2023)
Direct numerical simulations of stratified open channel flows subject to a varying surface heat flux are performed. The influence of the diurnal heating time on the spatial and temporal variation of mixing in the flow and the characteristics of the mean flow state are examined. The control parameters are the bulk stability parameter $$λ_{B}$$ λ B , defined through the ratio of the channel height $$δ$$ δ and a bulk Obukhov length scale $$\mathscr{L}_{B}$$ L B , and the diurnal time scale $$\hat{t}$$ t ^ , defined as the ratio of the heating time to an eddy turnover time. The Prandtl number Pr and Reynolds number $$Re_{τ}$$ R e τ have values of 1 and 400. Simulations are performed over $$\hat{t} = 1$$ t ^ = 1 to 24 and $$λ_{B} = 0.6$$ λ B = 0.6 to 26. Two key flow features are used to classify the flow regimes observed, namely the laminar layer depth (LLD) and stratified layer depth (SLD) where the LLD is defined as the depth from the free surface when the buoyancy Reynolds number $$Re_{B} ≈ 7$$ R e B ≈ 7 and the SLD is the depth from the free surface when the turbulent Froude number $$Fr ≈ 1$$ F r ≈ 1 . This study attempts to characterise how these length scales vary across the diel cycle. The LLD is a viscous length scale and a regime map of a viscous parameter, the bulk Obhukov Reynolds number $$Re_\mathscr{L}$$ R e L , and $$\hat{t}$$ t ^ is presented to classify the LLD behaviour. A regime map of $$λ _{B}$$ λ B and $$\hat{t}$$ t ^ is presented to classify the behaviour of the SLD. Three classifications for each layer depth behaviour within a diel cycle form the basis of the regime maps for this paper: a neutral flow where the LLD or SLD does not exist (denoted by NL and NS), a stratified flow where the LLD or SLD are diurnally varying (denoted as DL and DS) and a persistent layer of the LLD or SLD (denoted as PL and PS). The transition between the NL to DL is $$\hat{t} \propto Re_{\mathscr{L}}^{4.5}$$ t ^ ∝ R e L 4.5 , DL to PL is $$\hat{t} \propto Re_{\mathscr{L}}^{- 0.5}$$ t ^ ∝ R e L - 0.5 , NS to DS is $$\hat{t} \propto λ _{B}^{0}$$ t ^ ∝ λ B 0 and DS to PS is $$\hat{t} \propto λ _{B}^{1}$$ t ^ ∝ λ B 1 . The regime maps may be used as a predictive tool to determine when suppressed mixing regimes occur in rivers. At each flow depth, the flow sweeps though a range of mixing states across the diel cycle. The local mixing efficiency are briefly assessed and found to scale well with the instantaneous $$Fr$$ Fr number according to the regimes proposed by Garanaik and Venayagamoorthy ( J. Fluid Mech. , vol. 867, 2019, pp. 323-333).

Understanding the effect of metamictization on the efficiency of zircon milling - Matthew J. Smith; Emma Jones; Stuart Blackburn; Richard W. Greenwood (Minerals Engineering, 2023)

Modeling airborne pollen concentrations at an urban scale with pollen release from individual trees - Daniel S. W. Katz; Alan P. Baptist; Stuart A. Batterman (Aerobiologia, 2023)

Anthropogenic nitrogen pollution threats and challenges to the health of South Asian coral reefs - Stuart C. Painter; Yuri Artioli; Fathimath Hana Amir; Jessica Arnull; Raja S. Ganeshram; Nizam Ibrahim; V. Deepak Samuel; R.S. Robin; R. Raghuraman; R. Purvaja; R. Ramesh; Arjan Rajasuriya; et al. (Frontiers in Marine Science, 2023)
Nitrogen pollution is a widespread and growing problem in the coastal waters of South Asia yet the ecological impacts on the region’s coral ecosystems are currently poorly known and understood. South Asia hosts just under 7% of global coral reef coverage but has experienced significant and widespread coral loss in recent decades. The extent to which this coral ecosystem decline at the regional scale can be attributed to the multiple threats posed by nitrogen pollution has been largely overlooked in the literature. Here, we assess the evidence for nitrogen pollution impacts on corals in the central Indian Ocean waters of India, Sri Lanka and the Maldives. We find that there is currently limited evidence with which to clearly demonstrate widespread impacts on coral reefs from nitrogen pollution, including from its interactions with other stressors such as seawater warming. However, this does not prove there are no significant impacts, but rather it reflects the paucity of appropriate observations and related understanding of the range of potential impacts of nitrogen pollution at individual, species and ecosystem levels. This situation presents significant research, management and conservation challenges given the wide acceptance that such pollution is problematic. Following from this, we recommend more systematic collection and sharing of robust observations, modelling and experimentation to provide the baseline on which to base prescient pollution control action.

Controlling common carp (Cyprinus carpio): barriers, biological traits, and selective fragmentation - M. L. Piczak; P. A. Bzonek; T. C. Pratt; P. W. Sorensen; I. G. Stuart; T. Theÿsmeÿer; N. E. Mandrak; J. D. Midwood; S. J. Cooke (Biological Invasions, 2023)

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

Inhibitory mechanisms on dry anaerobic digestion: Ammonia, hydrogen and propionic acid relationship - Ildefonso Rocamora; Stuart T. Wagland; Francis Hassard; Raffaella Villa; Miriam Peces; Edmon W. Simpson; Oliver Fernández; Yadira Bajón-Fernández (Waste Management, 2023)

Monitoring and modeling dispersal of a submerged nearshore berm at the mouth of the Columbia River, USA - Andrew W. Stevens; Hans R. Moritz; Edwin P.L. Elias; Guy R. Gelfenbaum; Peter R. Ruggiero; Stuart G. Pearson; James M. McMillan; George M. Kaminsky (Coastal Engineering, 2023)

Global assessment of chemical quality of drinking water: The case of trihalomethanes - Cristina M Villanueva; Iro Evlampidou; Fathelrahman Ibrahim; Carolina Donat-Vargas; Antonia Valentin; Anca-Maria Tugulea; Shinya Echigo; Dragana Jovanovic; Albert T Lebedev; Mildred Lemus-Pérez; Manuel Rodriguez-Susa; Arben Luzati; et al. (Water Research, 2023)

An assessment of the validity and reliability of the P022–P version of e-Celsius core temperature capsules - Thomas W. Service; Katerina Junker; Breanna Service; Cory J. Coehoorn; Marisa Harrington; Steven Martin; Lynneth A. Stuart-Hill (Journal of Thermal Biology, 2023)

Pilot-scale phosphate recovery from wastewater to create a fertiliser product: An integrated assessment of adsorbent performance and quality - Sabolc Pap; Huiyi Zhang; Aleksandra Bogdan; Derek T. Elsby; Stuart W. Gibb; Barbara Bremner; Mark A. Taggart (Water Research, 2023)

Range and extinction dynamics of the steppe bison in Siberia: A pattern‐oriented modelling approach - July A. Pilowsky; Sean Haythorne; Stuart C. Brown; Mario Krapp; Edward Armstrong; Barry W. Brook; Carsten Rahbek; Damien A. Fordham (Global Ecology and Biogeography, 2022)
Aim To determine the ecological processes and drivers of range collapse, population decline and eventual extinction of the steppe bison in Eurasia. Location Siberia. Time period Pleistocene and Holocene. Major taxa studied Steppe bison ( Bison priscus ). Methods We configured 110,000 spatially explicit population models (SEPMs) of climate–human–steppe bison interactions in Siberia, which we ran at generational time steps from 50,000 years before present. We used pattern‐oriented modelling (POM) and fossil‐based inferences of distribution and demographic change of steppe bison to identify which SEPMs adequately simulated important interactions between ecological processes and biological threats. These “best models” were then used to disentangle the mechanisms that were integral in the population decline and later extinction of the steppe bison in its last stronghold in Eurasia. Results Our continuous reconstructions of the range and extinction dynamics of steppe bison were able to reconcile inferences of spatio‐temporal occurrence and the timing and location of extinction in Siberia based on hundreds of radiocarbon‐dated steppe bison fossils. We showed that simulating the ecological pathway to extinction for steppe bison in Siberia in the early Holocene required very specific ecological niche constraints, demographic processes and a constrained synergy of climate and human hunting dynamics during the Pleistocene–Holocene transition. Main conclusions Ecological processes and drivers that caused ancient population declines of species can be reconstructed at high spatio‐temporal resolutions using SEPMs and POM. Using this approach, we found that climatic change and hunting by humans are likely to have interacted with key ecological processes to cause the extinction of the steppe bison in its last refuge in Eurasia.

Clarifying the evidence for microbial‐ and plant‐derived soil organic matter, and the path toward a more quantitative understanding - Emily D. Whalen; A. Stuart Grandy; Noah W. Sokol; Marco Keiluweit; Jessica Ernakovich; Richard G. Smith; Serita D. Frey (Global Change Biology, 2022)
Predicting and mitigating changes in soil carbon (C) stocks under global change requires a coherent understanding of the factors regulating soil organic matter (SOM) formation and persistence, including knowledge of the direct sources of SOM (plants vs. microbes). In recent years, conceptual models of SOM formation have emphasized the primacy of microbial‐derived organic matter inputs, proposing that microbial physiological traits (e.g., growth efficiency) are dominant controls on SOM quantity. However, recent quantitative studies have challenged this view, suggesting that plants make larger direct contributions to SOM than is currently recognized by this paradigm. In this review, we attempt to reconcile these perspectives by highlighting that variation across estimates of plant‐ versus microbial‐derived SOM may arise in part from methodological limitations. We show that all major methods used to estimate plant versus microbial contributions to SOM have substantial shortcomings, highlighting the uncertainty in our current quantitative estimates. We demonstrate that there is significant overlap in the chemical signatures of compounds produced by microbes, plant roots, and through the extracellular decomposition of plant litter, which introduces uncertainty into the use of common biomarkers for parsing plant‐ and microbial‐derived SOM, especially in the mineral‐associated organic matter (MAOM) fraction. Although the studies that we review have contributed to a deeper understanding of microbial contributions to SOM, limitations with current methods constrain quantitative estimates. In light of recent advances, we suggest that now is a critical time to re‐evaluate long‐standing methods, clearly define their limitations, and develop a strategic plan for improving the quantification of plant‐ and microbial‐derived SOM. From our synthesis, we outline key questions and challenges for future research on the mechanisms of SOM formation and stabilization from plant and microbial pathways.

Impact of bacterial strain acquisition in the lung of patients with COPD: the AERIS study - Lucio Malvisi; Aparna Yarraguntla; Marie-Cécile Mortier; Karen Osman; David W. Cleary; Béatrice Sente; Thierry G. Pascal; Vincent Weynants; Stuart C. Clarke; Laura Taddei; Tom M. A. Wilkinson; Jeanne-Marie Devaster; et al. (Infectious Diseases, 2022)

Abattoir-based serological surveillance for transboundary and zoonotic diseases in cattle and swine in Cambodia: a pilot study in Phnom Penh province during 2019 and 2020 - Jarunee Siengsanan-Lamont; Sothyra Tum; Lida Kong; Paul W. Selleck; Laurence J. Gleeson; Stuart D. Blacksell (Tropical Animal Health and Production, 2022)
A pilot animal disease surveillance program was implemented at four abattoirs in Phnom Penh, Cambodia, between October 2019 and January 2020. A total of 1141 samples were collected from 477 cattle and 664 swine. Serological testing was performed using commercial antibody ELISA kits for zoonotic and high-impact animal diseases, namely brucellosis, Q fever, classical swine fever (CSF), porcine reproductive and respiratory syndrome (PRRS) and African swine fever (ASF). Only two samples tested positive for Brucella antibodies (0.2%, 95% CI 0.4–0.6, n = 1141). The seroprevalence of Q fever was 0.8% (95% CI 0.3–2.1, n = 477) in the cattle samples, while CSF, PRRS and ASF in pigs were 55.4% (95% CI 51.6–59.2, n = 655), 81.2% (95% CI 78.1–84.0, n = 655) and 2.6% (95% CI 1.6–4.1, n = 664), respectively. All 38 doubtful and 17 positive ASF antibody ELISA samples were negative when tested by real-time PCR. Univariate analyses demonstrated that the factor significantly associated with positive results of ASF was the abattoir location ( p -value = 0.002). Based on logistic regression models, significant risk factors for CSF were province of origin ( p -value = 1.7 × 10 −6 ), abattoir ( p -value = 3.6 × 10 −11 ) and PRRS positivity ( p -value = 0.004), and for PRRS were province of origin ( p -value = 0.0004) and CSF positivity ( p -value = 0.001). In conclusion, the seroprevalences of zoonotic diseases in this study were very low. The high prevalence of CSF and PRRS antibodies were most likely the result of vaccination. All ASF seropositive pigs, including those that gave equivocal results, originated from large-scale Cambodian-based commercial farms, as well as Thailand, which raises questions about possible illegal vaccination or low-pathogenicity ASF variants. The pilot abattoir serological surveillance program described here has the potential to provide a sentinel for incursions of novel and endemic pathogens, although further work is required to demonstrate its capacity to provide information on the longitudinal disease trends.

Earth stewardship: Shaping a sustainable future through interacting policy and norm shifts - F. Stuart Chapin; Elke U. Weber; Elena M. Bennett; Reinette Biggs; Jeroen van den Bergh; W. Neil Adger; Anne-Sophie Crépin; Stephen Polasky; Carl Folke; Marten Scheffer; Kathleen Segerson; John M. Anderies; et al. (Ambio, 2022)
Transformation toward a sustainable future requires an earth stewardship approach to shift society from its current goal of increasing material wealth to a vision of sustaining built, natural, human, and social capital—equitably distributed across society, within and among nations. Widespread concern about earth’s current trajectory and support for actions that would foster more sustainable pathways suggests potential social tipping points in public demand for an earth stewardship vision. Here, we draw on empirical studies and theory to show that movement toward a stewardship vision can be facilitated by changes in either policy incentives or social norms. Our novel contribution is to point out that both norms and incentives must change and can do so interactively. This can be facilitated through leverage points and complementarities across policy areas, based on values, system design, and agency. Potential catalysts include novel democratic institutions and engagement of non-governmental actors, such as businesses, civic leaders, and social movements as agents for redistribution of power. Because no single intervention will transform the world, a key challenge is to align actions to be synergistic, persistent, and scalable.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Next‐generation phylogeography resolves post‐glacial colonization patterns in a widespread carnivore, the red fox ( Vulpes vulpes ), in Europe - Allan D. McDevitt; Ilaria Coscia; Samuel S. Browett; Aritz Ruiz‐González; Mark J. Statham; Iwona Ruczyńska; Liam Roberts; Joanna Stojak; Alain C. Frantz; Karin Norén; Erik O. Ågren; Jane Learmount; et al. (Molecular Ecology, 2022)
Carnivores tend to exhibit a lack of (or less pronounced) genetic structure at continental scales in both a geographic and temporal sense and this can confound the identification of post‐glacial colonization patterns in this group. In this study we used genome‐wide data (using genotyping by sequencing [GBS]) to reconstruct the phylogeographic history of a widespread carnivore, the red fox ( Vulpes vulpes ), by investigating broad‐scale patterns of genomic variation, differentiation and admixture amongst contemporary populations in Europe. Using 15,003 single nucleotide polymorphisms (SNPs) from 524 individuals allowed us to identify the importance of refugial regions for the red fox in terms of endemism (e.g., Iberia). In addition, we tested multiple post‐glacial recolonization scenarios of previously glaciated regions during the Last Glacial Maximum using an Approximate Bayesian Computation (ABC) approach that were unresolved from previous studies. This allowed us to identify the role of admixture from multiple source population post‐Younger Dryas in the case of Scandinavia and ancient land‐bridges in the colonization of the British Isles. A natural colonization of Ireland was deemed more likely than an ancient human‐mediated introduction as has previously been proposed and potentially points to a larger mammalian community on the island in the early post‐glacial period. Using genome‐wide data has allowed us to tease apart broad‐scale patterns of structure and diversity in a widespread carnivore in Europe that was not evident from using more limited marker sets and provides a foundation for next‐generation phylogeographic studies in other non‐model species.

Setting priorities for climate change adaptation of Critical Sites in the Africa‐Eurasian waterbird flyways - Frank T. Breiner; Mira Anand; Stuart H. M. Butchart; Martina Flörke; Etienne Fluet‐Chouinard; Antoine Guisan; Lammert Hilarides; Victoria R. Jones; Mikhail Kalyakin; Bernhard Lehner; Merijn van Leeuwen; James W. Pearce‐Higgins; et al. (Global Change Biology, 2022)
Despite their importance for biodiversity and ecosystem services, wetlands are among the most threatened ecosystems globally. The conservation of many migratory waterbirds depends on the conservation of a network of key sites along their flyways. However, the suitability of these sites is changing under climate change, and it is important that management of individual sites in the network adapts to these changes. Using bioclimatic models that also account for changes in inundation, we found that projected climate change will reduce habitat suitability for waterbirds at 57.5% of existing Critical Sites within Africa‐Eurasia, varying from 20.1% in Eastern Europe to 87.0% in Africa. African and Middle East sites are particularly threatened, comprising 71 of the 100 most vulnerable sites. By highlighting priority sites for conservation and classifying Critical Sites into Climate Change Adaptation Strategy (CCAS) classes, our results can be used to support the climate change adaptation of both individual sites and the entire site network.

Combining Statistical Design with Deterministic Modelling to Assess the Effect of Site-Specific Factors on the Extent of Landslides - Vincent Lemiale; Carolyn Huston; Stuart Mead; David L. J. Alexander; Paul W. Cleary; Deepak Adhikary; Gary W. Delaney (Rock Mechanics and Rock Engineering, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Fecal steroids as a potential tool for conservation paleobiology in East Africa - Andrew C. Kemp; Christopher H. Vane; Alexander W. Kim; Christopher L. Dutton; Amanda L. Subalusky; Stuart K. Kemp; Andrew C. Parnell (Biodiversity and Conservation, 2022)

Cover Image - Damien A. Fordham; Stuart C. Brown; H. Reşit Akçakaya; Barry W. Brook; Sean Haythorne; Andrea Manica; Kevin T. Shoemaker; Jeremy J. Austin; Benjamin Blonder; Julia Pilowsky; Carsten Rahbek; David Nogues‐Bravo (Ecology Letters, 2022)

Process‐explicit models reveal pathway to extinction for woolly mammoth using pattern‐oriented validation - Damien A. Fordham; Stuart C. Brown; H. Reşit Akçakaya; Barry W. Brook; Sean Haythorne; Andrea Manica; Kevin T. Shoemaker; Jeremy J. Austin; Benjamin Blonder; July A. Pilowsky; Carsten Rahbek; David Nogues‐Bravo (Ecology Letters, 2022)
Pathways to extinction start long before the death of the last individual. However, causes of early stage population declines and the susceptibility of small residual populations to extirpation are typically studied in isolation. Using validated process‐explicit models, we disentangle the ecological mechanisms and threats that were integral in the initial decline and later extinction of the woolly mammoth. We show that reconciling ancient DNA data on woolly mammoth population decline with fossil evidence of location and timing of extinction requires process‐explicit models with specific demographic and niche constraints, and a constrained synergy of climatic change and human impacts. Validated models needed humans to hasten climate‐driven population declines by many millennia, and to allow woolly mammoths to persist in mainland Arctic refugia until the mid‐Holocene. Our results show that the role of humans in the extinction dynamics of woolly mammoth began well before the Holocene, exerting lasting effects on the spatial pattern and timing of its range‐wide extinction.

Data challenges for future plant gene editing: expert opinion - Rim Lassoued; Diego M. Macall; Stuart J. Smyth; Peter W. B. Phillips; Hayley Hesseln (Transgenic Research, 2021)
Agricultural data in its multiple forms are ubiquitous. With progress in crop and input monitoring systems and price reductions over the past decade, data are now being captured at an unprecedented rate. Once compiled, organized and analyzed, these data are capable of providing valuable insights into much of the agri-food supply chain. While much of the focus is on precision farming, agricultural data applications coupled with gene editing tools hold the potential to enhance crop performance and global food security. Yet, digitization of agriculture is a double-edged sword as it comes with inherent security and privacy quandaries. Infrastructure, policies, and practices to better harness the value of data are still lacking. This article reports expert opinions about the potential challenges regarding the use of data relevant to the development and approval of new crop traits as well as mechanisms employed to manage and protect data. While data could be of great value, issues of intellectual property and accessibility surround many of its forms. The key finding of this research is that surveyed experts optimistically report that by 2030, the synergy of computing power and genome editing could have profound effects on the global agri-food system, but that the European Union may not participate fully in this transformation.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Fires slow population declines of a long-lived prairie plant through multiple vital rates - Scott W. Nordstrom; Amy B. Dykstra; Stuart Wagenius (Oecologia, 2021)

Seroepidemiology of Foot and Mouth Disease using passive surveillance techniques in selected provinces of Lao PDR - Jarunee Siengsanan-Lamont; Bounlom Douangngeun; Watthana Theppangna; Syseng Khounsy; Phouvong Phommachanh; Somjai Kamolsiripichaiporn; Romphruke Udon; Kingkarn Boonsuya Seeyo; Paul W. Selleck; Nina Matsumoto; Laurence J. Gleeson; Stuart D. Blacksell (Tropical Animal Health and Production, 2021)
Foot and Mouth Disease (FMD) is a high-impact, contagious transboundary animal disease that is endemic in Southeast Asia. Abattoir samples were routinely collected in six selected provinces between March and December 2019. A total of 1280 samples of abattoir animals were tested for FMD Non-Structural Protein (NSP) antibodies to indicate natural infections. Overall, 22.8% were seropositive for FMD NSP antibodies while seroprevalence of cattle ( n = 469), buffalo ( n = 214), and pigs ( n = 597) were 44.6%, 35.0%, and 1.3%, respectively. The highest seroprevalence destination province was Xiengkhouang (35.3% of 272 samples), followed by Savannakhet (27.0% of 244 samples). Risk factors for evidence of natural infection identified by a multivariate logistic regression model included age groups ( p -value = 0.02) and origin provinces ( p -value = 2.8 × 10 −5 ) of the animals. There were significant differences of FMD NSP seroprevalence between age groups and origin provinces of the animals. The odds ratio of a seropositive result in the less than 1 year old group was 2.5 (95% CI; 1.4, 4.4) when compared to the 3–4 years old group, while the odds ratios for animals that originated from Khammouane and Xiengkhouang provinces were 4.5 (95% CI; 1.1, 18.7) and 2.4 (95% CI; 1.4, 4.1), respectively, when compared to Champasak province. Serotype-specific antibody ELISA for 44 NSP antibody–positive samples revealed evidence of FMD serotypes O and A virus circulation in some provinces. Despite the passive abattoir survey providing useful information on FMD virus previous exposure and geographic locations of the animals, timely information on FMD virus circulation and distribution is also crucial to an effective control program. Alternative approaches to increase the cost-effectiveness of the surveillance network are also discussed.

Sexual Mismatch Between Vessel-Associated Foraging and Discard Consumption in a Marine Top Predator - Joan Giménez; Gavin E. Arneill; Ashley Bennison; Enrico Pirotta; Hans D. Gerritsen; Thomas W. Bodey; Stuart Bearhop; Keith C. Hamer; Stephen Votier; Mark Jessopp (Frontiers in Marine Science, 2021)
Sex differences in diet and foraging behaviour are common in sexually dimorphic species, often driven by differences in the cost of locomotion or ability to exploit different ecological niches. However, sex-specific foraging strategies also occur in monomorphic or slightly dimorphic species where the drivers are poorly understood. Here, we study sex differences in foraging of northern gannets ( Morus bassanus ), where females are only slightly heavier than males. Using concurrently tracked gannets (298 full foraging trips from 81 individuals) and fishing vessels across 5 years, we quantify individual-based vessel-associated putative foraging, and relate this to discard consumption. We found a significant positive relationship between time spent in vessel-associated foraging and discard consumption for both sexes. However, while females showed greater proportions of vessel-associated foraging than males, discarded fish contributed less to the diet of females in all years. These results contrast with previous suggestions that female gannets interact with vessels less often than males, and are consistent with competitive exclusion of females from trawler-associated discards. Our findings give insight into sexual differences in foraging behaviour in the absence of dimorphism that are necessary to predict their response to environmental and anthropogenic changes.

Ecotrons: Powerful and versatile ecosystem analysers for ecology, agronomy and environmental science - Jacques Roy; François Rineau; Hans J. De Boeck; Ivan Nijs; Thomas Pütz; Samuel Abiven; John A. Arnone; Craig V. M. Barton; Natalie Beenaerts; Nicolas Brüggemann; Matteo Dainese; Timo Domisch; et al. (Global Change Biology, 2021)
Ecosystems integrity and services are threatened by anthropogenic global changes. Mitigating and adapting to these changes require knowledge of ecosystem functioning in the expected novel environments, informed in large part through experimentation and modelling. This paper describes 13 advanced controlled environment facilities for experimental ecosystem studies, herein termed ecotrons, open to the international community. Ecotrons enable simulation of a wide range of natural environmental conditions in replicated and independent experimental units while measuring various ecosystem processes. This capacity to realistically control ecosystem environments is used to emulate a variety of climatic scenarios and soil conditions, in natural sunlight or through broad‐spectrum lighting. The use of large ecosystem samples, intact or reconstructed, minimizes border effects and increases biological and physical complexity. Measurements of concentrations of greenhouse trace gases as well as their net exchange between the ecosystem and the atmosphere are performed in most ecotrons, often quasi continuously. The flow of matter is often tracked with the use of stable isotope tracers of carbon and other elements. Equipment is available for measurements of soil water status as well as root and canopy growth. The experiments ran so far emphasize the diversity of the hosted research. Half of them concern global changes, often with a manipulation of more than one driver. About a quarter deal with the impact of biodiversity loss on ecosystem functioning and one quarter with ecosystem or plant physiology. We discuss how the methodology for environmental simulation and process measurements, especially in soil, can be improved and stress the need to establish stronger links with modelling in future projects. These developments will enable further improvements in mechanistic understanding and predictive capacity of ecotron research which will play, in complementarity with field experimentation and monitoring, a crucial role in exploring the ecosystem consequences of environmental changes.

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Global root traits (GRooT) database - Nathaly R. Guerrero‐Ramírez; Liesje Mommer; Grégoire T. Freschet; Colleen M. Iversen; M. Luke McCormack; Jens Kattge; Hendrik Poorter; Fons van der Plas; Joana Bergmann; Thom W. Kuyper; Larry M. York; Helge Bruelheide; et al. (Global Ecology and Biogeography, 2021)
Motivation Trait data are fundamental to the quantitative description of plant form and function. Although root traits capture key dimensions related to plant responses to changing environmental conditions and effects on ecosystem processes, they have rarely been included in large‐scale comparative studies and global models. For instance, root traits remain absent from nearly all studies that define the global spectrum of plant form and function. Thus, to overcome conceptual and methodological roadblocks preventing a widespread integration of root trait data into large‐scale analyses we created the Global Root Trait (GRooT) Database. GRooT provides ready‐to‐use data by combining the expertise of root ecologists with data mobilization and curation. Specifically, we (a) determined a set of core root traits relevant to the description of plant form and function based on an assessment by experts, (b) maximized species coverage through data standardization within and among traits, and (c) implemented data quality checks. Main types of variables contained GRooT contains 114,222 trait records on 38 continuous root traits. Spatial location and grain Global coverage with data from arid, continental, polar, temperate and tropical biomes. Data on root traits were derived from experimental studies and field studies. Time period and grain Data were recorded between 1911 and 2019. Major taxa and level of measurement GRooT includes root trait data for which taxonomic information is available. Trait records vary in their taxonomic resolution, with subspecies or varieties being the highest and genera the lowest taxonomic resolution available. It contains information for 184 subspecies or varieties, 6,214 species, 1,967 genera and 254 families. Owing to variation in data sources, trait records in the database include both individual observations and mean values. Software format GRooT includes two csv files. A GitHub repository contains the csv files and a script in R to query the database.

Coexistence barriers confine the poleward range of a globally distributed plant - David W. Armitage; Stuart E. Jones (Ecology Letters, 2020)
In the study of factors shaping species' poleward range boundaries, climatic constraints are often assigned greater importance than biotic interactions such as competition. However, theory suggests competition can truncate a species' fundamental niche in harsh environments. We test this by challenging a mechanistic niche model – containing explicit competition terms – to predict the poleward range boundaries of two globally distributed, ecologically similar aquatic plant species. Mechanistic competition models accurately predicted the northern range limits of our study species, outperforming competition‐free mechanistic models and matching the predictive ability of statistical niche models fit to occurrence records. Using the framework of modern coexistence theory, we found that relative nonlinearity in competitors' responses to temperature fluctuations maintains their coexistence boundary, highlighting the importance of this fluctuation‐dependent mechanism. Our results support a more nuanced, interactive role of climate and competition in determining range boundaries, and illustrate a practical, process‐based approach to understanding the determinants of range limits.

Teatime in the Serengeti: macrodetritivores sustain recalcitrant plant litter decomposition across human-modified tropical savannahs - Anders Sundsdal; Bente J. Graae; James D. M. Speed; John Bukombe; Philipo Jacob Mtweve; Marit K. Arneberg; Vilde L. Haukenes; Ragnhild T. Grevskott; Stuart W. Smith (Plant and Soil, 2020)
Background and aims Intensification of savannah land-use is predicted to negatively influence soil biodiversity and functioning such as litter decomposition by detritivores. Loss of macrodetritivores, particularly termites, may be problematic in drier savannahs due to the capacity of macrodetritivores to sustain litter decomposition. Here we investigate how human land-use and spatiotemporal rainfall influence the contribution of macrodetritivores to plant litter decomposition. Methods We measured decomposition using globally standardized litter: labile green and recalcitrant rooibos tea litter. The contribution of macrodetritivores to litter decomposition was determined through exclusion using meshed litterbags. Litter decomposition was determined in agricultural land, pastureland and wildlife protected areas during both wet and dry seasons and in mesic and wet rainfall regions across the borders of the Serengeti National Park, Tanzania. Results Macrodetritivores consumed recalcitrant rooibos and mainly avoided labile green tea litter. On average macrodetritivores enhanced recalcitrant litter decomposition by 22%, but litter mass loss varied across land-uses, typically being higher on agricultural and pastureland compared to wildlife protected areas, and was sustained during periods of water scarcity. However, we observed instances of higher decomposition of recalcitrant litter by macrodetritivores in wildlife protected areas. In contrast, litter decomposition by microbes and microdetritivores was more constrained by seasonal and regional water availability with a minor influence of land-use. Conclusion We found that moderate human-modification of savannahs is compatible with macrodetritivore litter decomposition. As savannahs become more intensely used by humans, raising ecological awareness among agropastoralist is required to ensure continued contribution of macrodetritivores to litter decomposition.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Urban-scale variation in pollen concentrations: a single station is insufficient to characterize daily exposure - Daniel S. W. Katz; Stuart A. Batterman (Aerobiologia, 2020)

Pollen production for 13 urban North American tree species: allometric equations for tree trunk diameter and crown area - Daniel S. W. Katz; Jonathan R. Morris; Stuart A. Batterman (Aerobiologia, 2020)

Capacity challenges in water quality monitoring: understanding the role of human development - Sabrina Kirschke; Tamara Avellán; Ilona Bärlund; Janos J. Bogardi; Laurence Carvalho; Deborah Chapman; Chris W. S. Dickens; Kenneth Irvine; SungBong Lee; Thomas Mehner; Stuart Warner (Environmental Monitoring and Assessment, 2020)
Monitoring the qualitative status of freshwaters is an important goal of the international community, as stated in the Sustainable Development Goal (SDGs) indicator 6.3.2 on good ambient water quality. Monitoring data are, however, lacking in many countries, allegedly because of capacity challenges of less-developed countries. So far, however, the relationship between human development and capacity challenges for water quality monitoring have not been analysed systematically. This hinders the implementation of fine-tuned capacity development programmes for water quality monitoring. Against this background, this study takes a global perspective in analysing the link between human development and the capacity challenges countries face in their national water quality monitoring programmes. The analysis is based on the latest data on the human development index and an international online survey amongst experts from science and practice. Results provide evidence of a negative relationship between human development and the capacity challenges to meet SDG 6.3.2 monitoring requirements. This negative relationship increases along the course of the monitoring process, from defining the enabling environment, choosing parameters for the collection of field data, to the analytics and analysis of five commonly used parameters (DO, EC, pH, TP and TN). Our assessment can be used to help practitioners improve technical capacity development activities and to identify and target investment in capacity development for monitoring.

Synthesis optimisation and characterisation of chitosan-calcite adsorbent from fishery-food waste for phosphorus removal - Sabolc Pap; Caroline Kirk; Barbara Bremner; Maja Turk Sekulic; Stuart W. Gibb; Snezana Maletic; Mark A. Taggart (Environmental Science and Pollution Research, 2020)
Here, Box-Behnken design (BBD) approaches were utilised to optimise synthesis methodology for the chitosan-calcite rich adsorbent (CCM) made from fishery-food waste material (crab carapace), using low-temperature activation and potassium hydroxide (KOH). The effect of activation temperature, activation time and impregnation ratio was studied. The final adsorbent material was evaluated for its phosphorus (P) removal efficiency from liquid phase. Results showed that impregnation ratio was the most significant individual factor as this acted to increase surface deacetylation of the chitin (to chitosan) and increased the number of amine groups (–NH 2 ) in the chitosan chain. P removal efficiency approached 75.89% (at initial P concentration of 20 mg/L) under optimised experimental conditions, i.e. where the impregnation ratio for KOH:carapace (g/g) was 1:1, the activation temperature was 105 °C and the activation time was 150 min. Predicted responses were in good agreement with the experimental data. Additionally, the pristine and CCM material were further analysed using scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM/EDX), Brunauer-Emmett-Teller technique (BET), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and thermal gravimetric analysis (TGA). Characterisation showed enhancements in surface chemistry (introducing positively charged amine groups), textural properties and thermal stability of the CCM.

Transcriptional Profiling of Individual Airway Projecting Vagal Sensory Neurons - Stuart B. Mazzone; Luyi Tian; Aung Aung Kywe Moe; Matthew W. Trewella; Matthew E. Ritchie; Alice E. McGovern (Molecular Neurobiology, 2020)

Sexual reproduction in populations of Austropuccinia psidii - Alistair R. McTaggart; Esna du Plessis; Jolanda Roux; Irene Barnes; Stuart Fraser; Ginna M. Granados; Wellcome W. H. Ho; Louise S. Shuey; André Drenth (European Journal of Plant Pathology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Defining a spectrum of integrative trait‐based vegetation canopy structural types - Robert T. Fahey; Jeff W. Atkins; Christopher M. Gough; Brady S. Hardiman; Lucas E. Nave; Jason M. Tallant; Knute J. Nadehoffer; Christoph Vogel; Cynthia M. Scheuermann; Ellen Stuart‐Haëntjens; Lisa T. Haber; Alexander T. Fotis; et al. (Ecology Letters, 2019)
Vegetation canopy structure is a fundamental characteristic of terrestrial ecosystems that defines vegetation types and drives ecosystem functioning. We use the multivariate structural trait composition of vegetation canopies to classify ecosystems within a global canopy structure spectrum. Across the temperate forest sub‐set of this spectrum, we assess gradients in canopy structural traits, characterise canopy structural types (CST) and evaluate drivers and functional consequences of canopy structural variation. We derive CSTs from multivariate canopy structure data, illustrating variation along three primary structural axes and resolution into six largely distinct and functionally relevant CSTs. Our results illustrate that within‐ecosystem successional processes and disturbance legacies can produce variation in canopy structure similar to that associated with sub‐continental variation in forest types and eco‐climatic zones. The potential to classify ecosystems into CSTs based on suites of structural traits represents an important advance in understanding and modelling structure–function relationships in vegetated ecosystems.

Using time-series similarity measures to compare animal movement trajectories in ecology - Ian R. Cleasby; Ewan D. Wakefield; Barbara J. Morrissey; Thomas W. Bodey; Steven C. Votier; Stuart Bearhop; Keith C. Hamer (Behavioral Ecology and Sociobiology, 2019)
Identifying and understanding patterns in movement data are amongst the principal aims of movement ecology. By quantifying the similarity of movement trajectories, inferences can be made about diverse processes, ranging from individual specialisation to the ontogeny of foraging strategies. Movement analysis is not unique to ecology however, and methods for estimating the similarity of movement trajectories have been developed in other fields but are currently under-utilised by ecologists. Here, we introduce five commonly used measures of trajectory similarity: dynamic time warping (DTW), longest common subsequence (LCSS), edit distance for real sequences (EDR), Fréchet distance and nearest neighbour distance (NND), of which only NND is routinely used by ecologists. We investigate the performance of each of these measures by simulating movement trajectories using an Ornstein-Uhlenbeck (OU) model in which we varied the following parameters: (1) the point of attraction, (2) the strength of attraction to this point and (3) the noise or volatility added to the movement process in order to determine which measures were most responsive to such changes. In addition, we demonstrate how these measures can be applied using movement trajectories of breeding northern gannets ( Morus bassanus ) by performing trajectory clustering on a large ecological dataset. Simulations showed that DTW and Fréchet distance were most responsive to changes in movement parameters and were able to distinguish between all the different parameter combinations we trialled. In contrast, NND was the least sensitive measure trialled. When applied to our gannet dataset, the five similarity measures were highly correlated despite differences in their underlying calculation. Clustering of trajectories within and across individuals allowed us to easily visualise and compare patterns of space use over time across a large dataset. Trajectory clusters reflected the bearing on which birds departed the colony and highlighted the use of well-known bathymetric features. As both the volume of movement data and the need to quantify similarity amongst animal trajectories grow, the measures described here and the bridge they provide to other fields of research will become increasingly useful in ecology. Significance statement As the use of tracking technology increases, there is a need to develop analytical techniques to process such large volumes of data. One area in which this would be useful is the comparison of individual movement trajectories. In response, a variety of measures of trajectory similarity have been developed within the information sciences. However, such measures are rarely used by ecologists who may be unaware of them. To remedy this, we apply five common measures of trajectory similarity to both simulated data and real ecological dataset comprising of movement trajectories of breeding northern gannets. Dynamic time warping and Fréchet distance performed best on simulated data. Using trajectory similarity measures on our gannet dataset, we identified distinct foraging clusters centred on different bathymetric features, demonstrating one application of such similarity measures. As new technology and analysis techniques proliferate across ecology and the information sciences, closer ties between these fields promise further innovative analysis of movement data.

Opposing Indirect Effects of Domestic Herbivores on Saltmarsh Erosion - Jordi F. Pagès; Stuart R. Jenkins; Tjeerd J. Bouma; Elwyn Sharps; Martin W. Skov (Ecosystems, 2019)

Correction to: Heat attenuation and nutrient delivery by localized upwelling avoided coral bleaching mortality in northern Galapagos during 2015/2016 ENSO - Bernhard Riegl; Peter W. Glynn; Stuart Banks; Inti Keith; Fernando Rivera; Mariana Vera-Zambrano; Cecilia D’Angelo; Jörg Wiedenmann (Coral Reefs, 2019)

Heat attenuation and nutrient delivery by localized upwelling avoided coral bleaching mortality in northern Galapagos during 2015/2016 ENSO - Bernhard Riegl; Peter W. Glynn; Stuart Banks; Inti Keith; Fernando Rivera; Mariana Vera-Zambrano; Cecilia D’Angelo; Jörg Wiedenmann (Coral Reefs, 2019)

The Australian National Rabbit Database: 50 yr of population monitoring of an invasive species - Emilie Roy‐Dufresne; Miguel Lurgi; Stuart C. Brown; Konstans Wells; Brian Cooke; Greg Mutze; David Peacock; Phill Cassey; Dave Berman; Barry W. Brook; Susan Campbell; Tarnya Cox; et al. (Ecology, 2019)
With ongoing introductions into Australia since the 1700s, the European rabbit ( Oryctolagus cuniculus ) has become one of the most widely distributed and abundant vertebrate pests, adversely impacting Australia's biodiversity and agroeconomy. To understand the population and range dynamics of the species and its impacts better, occurrence and abundance data have been collected by researchers and citizens from sites covering a broad spectrum of climatic and environmental conditions in Australia. The lack of a common and accessible repository for these data has, however, limited their use in determining important spatiotemporal drivers of the structure and dynamics of the geographical range of rabbits in Australia. To meet this need, we created the Australian National Rabbit Database, which combines more than 50 yr of historical and contemporary survey data collected from throughout the range of the species in Australia. The survey data, obtained from a suite of complementary monitoring methods, were combined with high‐resolution weather, climate, and environmental information, and an assessment of data quality. The database provides records of rabbit occurrence (689,265 records) and abundance (51,241 records, >120 distinct sites) suitable for identifying the spatiotemporal drivers of the rabbit's distribution and for determining spatial patterns of variation in its key life‐history traits, including maximum rates of population growth. Because all data are georeferenced and date stamped, they can be coupled with information from other databases and spatial layers to explore the potential effects of rabbit occurrence and abundance on Australia's native wildlife and agricultural production. The Australian National Rabbit Database is an important tool for understanding and managing the European rabbit in its invasive range and its effects on native biodiversity and agricultural production. It also provides a valuable resource for addressing questions related to the biology, success, and impacts of invasive species more generally. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Negative frequency‐dependent growth underlies the stable coexistence of two cosmopolitan aquatic plants - David W. Armitage; Stuart E. Jones (Ecology, 2019)
Identifying and quantifying the mechanisms influencing species coexistence remains a major challenge for the study of community ecology. These mechanisms, which stem from species’ differential responses to competition and their environments, promote coexistence if they give each species a growth advantage when rare. Yet despite the widespread assumption that co‐occurring species stably coexist, there have been few empirical demonstrations in support of this claim. Likewise, coexistence is often assumed to result from interspecific differences in life‐history traits, but the relative contributions of these trait differences to coexistence are rarely quantified, particularly across environmental gradients. Using two widely co‐occurring and ecologically similar species of freshwater duckweed plants ( Spirodela polyrhiza and Lemna minor ), we tested hypotheses that interspecific differences in facultative dormancy behaviors, thermal reaction norms, and density‐dependent growth promote coexistence between these species, and that their relative influences on coexistence change as average temperatures and fluctuations around them vary. In competition experiments, we found strong evidence for negative frequency‐dependent growth across a range of both static and fluctuating temperatures, suggesting a critical role of fluctuation‐independent stabilization in coexistence. This negative frequency dependence could be explained by our observation that for both species, intraspecific competition was over 1.5 times stronger than interspecific competition, granting each species a low‐density growth advantage. Using an empirically parameterized competition model, we found that while coexistence was facilitated by environmental fluctuations, fluctuation‐independent stabilization via negative frequency dependence was crucial for coexistence. Conversely, the temporal storage effect, an important fluctuation‐dependent mechanism, was relatively weak in comparison. Contrary to expectations, differences in the species’ thermal reaction norms and dormancy behaviors did not significantly promote coexistence in fluctuating environments. Our results highlight how coexistence in two ubiquitous and ostensibly similar aquatic plants is not necessarily a product of their most obvious interspecific differences, and instead results from subtle niche differences causing negative frequency‐dependent growth, which acts consistently on both species across environmental gradients.

Benefits of genome-edited crops: expert opinion - Rim Lassoued; Diego Maximiliano Macall; Hayley Hesseln; Peter W. B. Phillips; Stuart J. Smyth (Transgenic Research, 2019)

VOC sources and exposures in nail salons: a pilot study in Michigan, USA - Lexuan Zhong; Stuart Batterman; Chad W. Milando (International Archives of Occupational and Environmental Health, 2019)

Precision and accuracy of Dahl‐Lea back‐calculated smolt lengths from adult scales of Atlantic salmon Salmo salar - Nora N. Hanson; Gordon W. Smith; Stuart J. Middlemas; Christopher D. Todd (Journal of Fish Biology, 2019)
Using tagged and recaptured Atlantic salmon Salmo salar (n = 106) the present analysis shows that the most commonly applied linear back‐calculation method for estimating past length, the Dahl‐Lea method, resulted in overestimation of the length of large smolts and underestimation of small smolts. A correction equation ( y = 0.53 x + 6.23) for estimating true smolt length ( y ) from lengths back‐calculated from adult scale measures ( x ) to account for these systematic discrepancies is proposed.

Variation in DNA methylation is associated with migratory phenotypes of lake sturgeon Acipenser fulvescens in the St. Clair River, MI, USA - Justine M. Whitaker; Amy B. Welsh; Darryl W. Hondorp; James C. Boase; George T. Merovich; Stuart Welsh; Charles Krueger (Journal of Fish Biology, 2018)
Lake sturgeon Acipenser fulvescens populations show a variety of movement patterns that are poorly understood. To compare two migratory phenotypes of A. fulvescens in the St. Clair River, MI, USA, multiple data types were analysed. Individual fish were classified into migratory phenotypes based on acoustic telemetry data collected 2012–2015. Acipenser fulvescens consistently showed movement from the St. Clair River upriver into Lake Huron or downriver into Lake St. Clair. The two migratory phenotypes were then compared for differences in morphometrics, genetics and epigenetics. Morphological differences based on linear measurements were not detected between phenotypes. Microsatellite data from 11 loci suggested one population with no genetic differentiation between migratory phenotypes. Our epigenetic results indicated that the migratory phenotypes are differentially methylated ( P A. fulvescens . Only one restriction site was identified to be driving the differential methylation ( P A. fulvescens , DNA methylation may play a role in the observed movement pattern variation. When combined with microsatellite and morphometric analyses, our results suggested that different migratory patterns may reflect phenotypic plasticity, allowing A. fulvescens to acclimate to short‐term environmental variability. Without an integrated approach, the role of epigenetics in the migratory phenotype of A. fulvescens may have been overlooked. Further characterization of migratory phenotypes could be important for management to conserve behavioural variation across the distribution of A. fulvescens and for design of stocking guidelines.

The adoption of automated phenotyping by plant breeders - Lana Awada; Peter W. B. Phillips; Stuart J. Smyth (Euphytica, 2018)
Phenomics or automated phenotyping (AP) is an emerging approach, identified as a priority for future crop breeding research. This approach promises to provide accurate, precise, fast, large-scale, and accumulated phenotyping data which when integrated with corresponding genomic and environmental data is expected to trigger a great leap forward in plant breeding. However, despite promising applications, AP adoption in plant breeding is still in its infancy. It is unclear to many plant breeders how or if much of the enormous volume, diversity, and velocity of imaging and remote-sensing data generated by AP is going to be usefully integrated into breeding programs. This paper develops an economical model of heterogeneous breeders’ decision-making to examine adoption decisions regarding whether to adopt AP or continue using conventional phenotyping. The results of this model indicate that many interlocking factors, including genetic gain/expected return, variable and sunk costs, subsequent rate of technology improvement, and breeders’ level of aversion to AP, are at work as breeders determine whether to adopt AP. This study also provides a numerical example to show the impact of breeders’ aversion toward the adoption of a new technology (e.g., AP) on the expected return generated from breeding a new wheat variety.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Performance of an elite, hybrid family of a northern × southern highbush cross (‘Draper’ × ‘Jewel’) - James F. Hancock; James W. Olmstead; Rachel A. Itle; Peter W. Callow; Stuart Neils-Kraft; Edmund J. Wheeler; Jozer Mangandi; Suneth S. Sooriyapathirana; Lisa J. Rowland; Ted A. Mackey; Nahla V. Bassil; Chad E. Finn (Euphytica, 2018)

A cross‐continental comparison of assemblages of seed‐ and fruit‐feeding insects in tropical rain forests: Faunal composition and rates of attack - Yves Basset; Chris Dahl; Richard Ctvrtecka; Sofia Gripenberg; Owen T. Lewis; Simon T. Segar; Petr Klimes; Héctor Barrios; John W. Brown; Sarayudh Bunyavejchewin; Buntika A. Butcher; Anthony I. Cognato; et al. (Journal of Biogeography, 2018)
Aim Insects feeding on seeds and fruits represent interesting study systems, potentially able to lower the fitness of their host plants. In addition to true seed eaters, a suite of insects feed on the fleshy parts of fruits. We examined the likelihood of community convergence in whole insect assemblages attacking seeds/fruits in three tropical rain forests. Location Three Forest GEO permanent forest plots within different biogeographical regions: Barro Colorado Island (Panama), Khao Chong (Thailand) and Wanang (Papua New Guinea). Methods We surveyed 1,186 plant species and reared 1.1 ton of seeds/fruits that yielded 80,600 insects representing at least 1,678 species. We assigned seeds/fruits to predation syndromes on the basis of plant traits relevant to insects, seed/fruit appearance and mesocarp thickness. Results We observed large differences in insect faunal composition, species richness and guild structure between our three study sites. We hypothesize that the high species richness of insect feeding on seeds/fruits in Panama may result from a conjunction of low plant species richness and high availability of dry fruits. Insect assemblages were weakly influenced by seed predation syndromes, both at the local and regional scale, and the effect of host phylogeny varied also among sites. At the driest site (Panama), the probability of seeds of a plant species being attacked depended more on seed availability than on the measured seed traits of that plant species. However, when seeds were attacked, plant traits shaping insect assemblages were difficult to identify and not related to seed availability. Main conclusions We observed only weak evidence of community convergence at the intercontinental scale among these assemblages. Our study suggests that seed eaters may be most commonly associated with dry fruits at relatively dry tropical sites where fleshy fruits may be less prevalent.

Ammonia‐oxidizing bacteria are the primary N 2 O producers in an ammonia‐oxidizing archaea dominated alkaline agricultural soil - Kelley A. Meinhardt; Nejc Stopnisek; Manmeet W. Pannu; Stuart E. Strand; Steven C. Fransen; Karen L. Casciotti; David A. Stahl (Environmental Microbiology, 2018)
Summary Most agricultural N 2 O emissions are a consequence of microbial transformations of nitrogen (N) fertilizer, and mitigating increases in N 2 O emission will depend on identifying microbial sources and variables influencing their activities. Here, using controlled microcosm and field studies, we found that synthetic N addition in any tested amount stimulated the production of N 2 O from ammonia‐oxidizing bacteria (AOB), but not archaea (AOA), from a bioenergy crop soil. The activities of these two populations were differentiated by N treatments, with abundance and activity of AOB increasing as nitrate and N 2 O production increased. Moreover, as N 2 O production increased, the isotopic composition of N 2 O was consistent with an AOB source. Relative N 2 O contributions by both populations were quantified using selective inhibitors and varying N availability. Complementary field analyses confirmed a positive correlation between N 2 O flux and AOB abundance with N application. Collectively, our data indicate that AOB are the major N 2 O producers, even with low N addition, and that better‐metered N application, complemented by selective inhibitors, could reduce projected N 2 O emissions from agricultural soils.

Air pollutant strategies to reduce adverse health impacts and health inequalities: a quantitative assessment for Detroit, Michigan - Sheena E. Martenies; Chad W. Milando; Stuart A. Batterman (Air Quality, Atmosphere & Health, 2018)

How complex should models be? Comparing correlative and mechanistic range dynamics models - Damien A. Fordham; Cleo Bertelsmeier; Barry W. Brook; Regan Early; Dora Neto; Stuart C. Brown; Sébastien Ollier; Miguel B. Araújo (Global Change Biology, 2018)
Criticism has been levelled at climate‐change‐induced forecasts of species range shifts that do not account explicitly for complex population dynamics. The relative importance of such dynamics under climate change is, however, undetermined because direct tests comparing the performance of demographic models vs. simpler ecological niche models are still lacking owing to difficulties in evaluating forecasts using real‐world data. We provide the first comparison of the skill of coupled ecological‐niche‐population models and ecological niche models in predicting documented shifts in the ranges of 20 British breeding bird species across a 40‐year period. Forecasts from models calibrated with data centred on 1970 were evaluated using data centred on 2010. We found that more complex coupled ecological‐niche‐population models (that account for dispersal and metapopulation dynamics) tend to have higher predictive accuracy in forecasting species range shifts than structurally simpler models that only account for variation in climate. However, these better forecasts are achieved only if ecological responses to climate change are simulated without static snapshots of historic land use, taken at a single point in time. In contrast, including both static land use and dynamic climate variables in simpler ecological niche models improve forecasts of observed range shifts. Despite being less skilful at predicting range changes at the grid‐cell level, ecological niche models do as well, or better, than more complex models at predicting the magnitude of relative change in range size. Therefore, ecological niche models can provide a reasonable first approximation of the magnitude of species' potential range shifts, especially when more detailed data are lacking on dispersal dynamics, demographic processes underpinning population performance, and change in land cover.

Alien plants as mediators of ecosystem services and disservices in urban systems: a global review - Luke J. Potgieter; Mirijam Gaertner; Christoph Kueffer; Brendon M. H. Larson; Stuart W. Livingstone; Patrick J. O’Farrell; David M. Richardson (Biological Invasions, 2017)

Are urban systems beneficial, detrimental, or indifferent for biological invasion? - Marc W. Cadotte; Simone Louise E. Yasui; Stuart Livingstone; J. Scott MacIvor (Biological Invasions, 2017)

Explaining ecosystem multifunction with evolutionary models - Marc W. Cadotte; Stuart W. Livingstone; Simone‐Louise E. Yasui; Russell Dinnage; Jin‐tian Li; Robin Marushia; James Santangelo; Wensheng Shu (Ecology, 2017)
Ecosystem function is the outcome of species interactions, traits, and niche overlap – all of which are influenced by evolution. However, it is not well understood how the tempo and mode of niche evolution can influence ecosystem function. In evolutionary models where either species differences accumulate through random drift in a single trait or species differences accumulate through divergent selection among close relatives, we should expect that ecosystem function is strongly related to diversity. However, when strong selection causes species to converge on specific niches or when novel traits that directly affect function evolve in some clades but not others, the relationship between diversity and ecosystem function might not be very strong. We test these ideas using a field experiment that established plant mixtures with differing phylogenetic diversities and we measured ten different community functions. We show that some functions were strongly predicted by species richness and mean pairwise phylogenetic distance ( MPD , a measure of phylogenetic diversity), including biomass production and the reduction of herbivore and pathogen damage in polyculture, while other functions had weaker (litter production and structural complexity) or nonsignificant relationships (e.g., flower production and arthropod abundance) with MPD and richness. However, these divergent results can be explained by different models of niche evolution. These results show that diversity‐ecosystem function relationships are the product of evolution, but that the nature of how evolution influences ecosystem function is complex.

Variations of leaf longevity in tropical moist forests predicted by a trait‐driven carbon optimality model - Xiangtao Xu; David Medvigy; Stuart Joseph Wright; Kaoru Kitajima; Jin Wu; Loren P. Albert; Giordane A. Martins; Scott R. Saleska; Stephen W. Pacala (Ecology Letters, 2017)
Leaf longevity ( LL ) varies more than 20‐fold in tropical evergreen forests, but it remains unclear how to capture these variations using predictive models. Current theories of LL that are based on carbon optimisation principles are challenging to quantitatively assess because of uncertainty across species in the ‘ageing rate:’ the rate at which leaf photosynthetic capacity declines with age. Here, we present a meta‐analysis of 49 species across temperate and tropical biomes, demonstrating that the ageing rate of photosynthetic capacity is positively correlated with the mass‐based carboxylation rate of mature leaves. We assess an improved trait‐driven carbon optimality model with in situ LL data for 105 species in two Panamanian forests. We show that our model explains over 40% of the cross‐species variation in LL under contrasting light environment. Collectively, our results reveal how variation in LL emerges from carbon optimisation constrained by both leaf structural traits and abiotic environment.

High stocks, but slow recovery, of ecosystem carbon in southern oceanic tussock grasslands - Stuart W. Smith; Susanna Karlsson (Polar Biology, 2017)

Genomic analysis of chimeric human cytomegalovirus vaccine candidates derived from strains Towne and Toledo - Nicolás M. Suárez; Betty Lau; George M. Kemble; Ronzo Lee; Edward S. Mocarski; Gavin W. G. Wilkinson; Stuart P. Adler; Michael A. McVoy; Andrew J. Davison (Virus Genes, 2017)

Quantitative trait loci controlling vegetative propagation traits mapped in European pear (Pyrus communis L.) - Mareike Knäbel; Adam P. Friend; John W. Palmer; Robert Diack; Susan E. Gardiner; Stuart Tustin; Robert Schaffer; Toshi Foster; David Chagné (Tree Genetics & Genomes, 2017)

Climate change as a long-term stressor for the fisheries of the Laurentian Great Lakes of North America - Paris D. Collingsworth; David B. Bunnell; Michael W. Murray; Yu-Chun Kao; Zachary S. Feiner; Randall M. Claramunt; Brent M. Lofgren; Tomas O. Höök; Stuart A. Ludsin (Reviews in Fish Biology and Fisheries, 2017)

Urban groundwater quality in sub-Saharan Africa: current status and implications for water security and public health - D. J. Lapworth; D. C. W. Nkhuwa; J. Okotto-Okotto; S. Pedley; M. E. Stuart; M. N. Tijani; J. Wright (Hydrogeology Journal, 2017)

Can greening of aquaculture sequester blue carbon? - Nesar Ahmed; Stuart W. Bunting; Marion Glaser; Mark S. Flaherty; James S. Diana (Ambio, 2017)

Does range‐restricted evolutionary history predict extinction risk? A case study in lizards - Giovanni Di Virgilio; Shawn W. Laffan; Stuart V. Nielsen; David G. Chapple (Journal of Biogeography, 2017)
Aim Conservation is often prioritized by identifying regional clusters of threatened or endemic species. Another approach is to assess the evolutionary distinctiveness of groups of taxa using phylodiversity measures. However, quantification of evolutionary history has traditionally not accounted for its uneven geographical distribution due to the variation in species ranges. We assess the efficacy of phylogenetic endemism ( PE ) to predict high extinction risk in comparison to estimates of species range restriction (weighted endemism, WE ) and phylogenetic diversity ( PD ). PE measures the relative range restriction of evolutionary history (lineages), while WE concentrates on the tips of the tree of life, treating all such branches as being of equal length. Location/Methods Using New Zealand's endemic skinks and geckos, we mapped the geographical variation in their extinction risk, PE , WE and PD and measured the extent to which extinction risk exhibited phylogenetic clustering for each group. Correlations between geographical concentrations of high skink and gecko extinction risk with PE , WE and PD were calculated. Results PE was predictive of spatial clusters of high extinction risk for geckos ( r 2 = 0.34, P 0.001) while WE was markedly less so ( r 2 = 0.19, P 0.001). The reverse applied to skinks, with WE most predictive of high risk ( r 2 = 0.26, P 0.001). The phylogenetic signal of extinction risk was significantly conserved for geckos, but was weaker and non‐significant for skinks. PE and WE were not predictive of low risk. PD was not predictive of risk. Main conclusions PE and related measures may be predictive of extinction risk when risk is phylogenetically conserved. Mapping the geographical variation in PE could be a useful first assessment of extinction risk for many groups because phylogenies are increasingly available, while full risk status categories are not. These findings might apply to other groups and locations and warrant further investigation.

Applying population and community ecology theory to advance understanding of belowground biogeochemistry - Robert W. Buchkowski; Mark A. Bradford; Andrew Stuart Grandy; Oswald J. Schmitz; William R. Wieder (Ecology Letters, 2017)
Approaches to quantifying and predicting soil biogeochemical cycles mostly consider microbial biomass and community composition as products of the abiotic environment. Current numerical approaches then primarily emphasise the importance of microbe–environment interactions and physiology as controls on biogeochemical cycles. Decidedly less attention has been paid to understanding control exerted by community dynamics and biotic interactions. Yet a rich literature of theoretical and empirical contributions highlights the importance of considering how variation in microbial population ecology, especially biotic interactions, is related to variation in key biogeochemical processes like soil carbon formation. We demonstrate how a population and community ecology perspective can be used to (1) understand the impact of microbial communities on biogeochemical cycles and (2) reframe current theory and models to include more detailed microbial ecology. Through a series of simulations we illustrate how density dependence and key biotic interactions, such as competition and predation, can determine the degree to which microbes regulate soil biogeochemical cycles. The ecological perspective and model simulations we present lay the foundation for developing empirical research and complementary models that explore the diversity of ecological mechanisms that operate in microbial communities to regulate biogeochemical processes.

Using CBPR to Extend Prostate Cancer Education, Counseling, and Screening Opportunities to Urban-Dwelling African-Americans - Levi Ross; Jarrett Johnson; Stacy W. Smallwood; John S. Luque; Stuart H. Tedders; Collins O. Airhihenbuwa; Terry Alford; Willie Underwood (Journal of Cancer Education, 2016)

Determinants of bird conservation‐action implementation and associated population trends of threatened species - David A. Luther; Thomas M. Brooks; Stuart H.M. Butchart; Matt W. Hayward; Marieke E. Kester; John Lamoreux; Amy Upgren (Conservation Biology, 2016)
Conservation actions, such as habitat protection, attempt to halt the loss of threatened species and help their populations recover. The efficiency and the effectiveness of actions have been examined individually. However, conservation actions generally occur simultaneously, so the full suite of implemented conservation actions should be assessed. We used the conservation actions underway for all threatened and near‐threatened birds of the world (International Union for Conservation of Nature Red List of Threatened Species) to assess which biological (related to taxonomy and ecology) and anthropogenic (related to geoeconomics) factors were associated with the implementation of different classes of conservation actions. We also assessed which conservation actions were associated with population increases in the species targeted. Extinction‐risk category was the strongest single predictor of the type of conservation actions implemented, followed by landmass type (continent, oceanic island, etc.) and generation length. Species targeted by invasive nonnative species control or eradication programs, ex situ conservation, international legislation, reintroduction, or education, and awareness‐raising activities were more likely to have increasing populations. These results illustrate the importance of developing a predictive science of conservation actions and the relative benefits of each class of implemented conservation action for threatened and near‐threatened birds worldwide.

Stable isotopes and mtDNA reveal niche segregation but no evidence of intergradation along a habitat gradient in the Lesser Whitethroat complex (Sylvia curruca; Passeriformes; Aves) - Stephen C. Votier; Simon Aspinall; Stuart Bearhop; David Bilton; Jason Newton; Per Alström; Paul Leader; Geoff Carey; Robert W. Furnes; Urban Olsson (Journal of Ornithology, 2016)

Importance of local values to successful conservation: response to Jacquet and Delon - Robin Naidoo; L. Chris Weaver; Richard W. Diggle; Greenwell Matongo; Greg Stuart‐Hill; Chris Thouless (Conservation Biology, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Complementary benefits of tourism and hunting to communal conservancies in Namibia - Robin Naidoo; L. Chris Weaver; Richard W. Diggle; Greenwell Matongo; Greg Stuart‐Hill; Chris Thouless (Conservation Biology, 2016)
Tourism and hunting both generate substantial revenues for communities and private operators in Africa, but few studies have quantitatively examined the trade‐offs and synergies that may result from these two activities. We evaluated financial and in‐kind benefit streams from tourism and hunting on 77 communal conservancies in Namibia from 1998 to 2013, where community‐based wildlife conservation has been promoted as a land‐use that complements traditional subsistence agriculture. We used data collected annually for all communal conservancies to characterize whether benefits were derived from hunting or tourism. We classified these benefits into 3 broad classes and examined how benefits flowed to stakeholders within communities under the status quo and under a simulated ban on hunting. Across all conservancies, total benefits from hunting and tourism increased at roughly the same rate, although conservancies typically started generating benefits from hunting within 3 years of formation as opposed to after 6 years for tourism. Disaggregation of data revealed that the main benefits from hunting were income for conservancy management and food in the form of meat for the community at large. The majority of tourism benefits were salaried jobs at lodges. A simulated ban on trophy hunting significantly reduced the number of conservancies that could cover their operating costs, whereas eliminating income from tourism did not have as severe an effect. Given that the benefits generated from hunting and tourism typically begin at different times in a conservancy's life‐span (earlier vs. later, respectively) and flow to different segments of local communities, these 2 activities together may provide the greatest incentives for conservation on communal lands in Namibia. A singular focus on either hunting or tourism would reduce the value of wildlife as a competitive land‐use option and have grave repercussions for the viability of community‐based conservation efforts in Namibia, and possibly other parts of Africa.

Incomplete coexistence systems and international food trade impacts - Stuart J. Smyth; Peter W. B. Phillips (Transgenic Research, 2015)

Long‐term individual foraging site fidelity—why some gannets don't change their spots - Ewan D. Wakefield; Ian R. Cleasby; Stuart Bearhop; Thomas W. Bodey; Rachel D. Davies; Peter I. Miller; Jason Newton; Stephen C. Votier; Keith C. Hamer (Ecology, 2015)
Many established models of animal foraging assume that individuals are ecologically equivalent. However, it is increasingly recognized that populations may comprise individuals who differ consistently in their diets and foraging behaviors. For example, recent studies have shown that individual foraging site fidelity (IFSF, when individuals consistently forage in only a small part of their population's home range) occurs in some colonial breeders. Short‐term IFSF could result from animals using a win–stay, lose–shift foraging strategy. Alternatively, it may be a consequence of individual specialization. Pelagic seabirds are colonial central‐place foragers, classically assumed to use flexible foraging strategies to target widely dispersed, spatiotemporally patchy prey. However, tracking has shown that IFSF occurs in many seabirds, although it is not known whether this persists across years. To test for long‐term IFSF and to examine alternative hypotheses concerning its cause, we repeatedly tracked 55 Northern Gannets ( Morus bassanus ) from a large colony in the North Sea within and across three successive breeding seasons. Gannets foraged in neritic waters, predictably structured by tidal mixing and thermal stratification, but subject to stochastic, wind‐induced overturning. Both within and across years, coarse to mesoscale (tens of kilometers) IFSF was significant but not absolute, and foraging birds departed the colony in individually consistent directions. Carbon stable isotope ratios in gannet blood tissues were repeatable within years and nitrogen ratios were also repeatable across years, suggesting long‐term individual dietary specialization. Individuals were also consistent across years in habitat use with respect to relative sea surface temperature and in some dive metrics, yet none of these factors accounted for IFSF. Moreover, at the scale of weeks, IFSF did not decay over time and the magnitude of IFSF across years was similar to that within years, suggesting that IFSF is not primarily the result of win–stay, lose–shift foraging. Rather, we hypothesize that site familiarity, accrued early in life, causes IFSF by canalizing subsequent foraging decisions. Evidence from this and other studies suggests that IFSF may be common in colonial central‐place foragers, with far‐reaching consequences for our attempts to understand and conserve these animals in a rapidly changing environment.

Combination of herbivore removal and nitrogen deposition increases upland carbon storage - Stuart W. Smith; David Johnson; Samuel L. O. Quin; Kyle Munro; Robin J. Pakeman; René van der Wal; Sarah J. Woodin (Global Change Biology, 2015)
Ecosystem carbon (C) accrual and storage can be enhanced by removing large herbivores as well as by the fertilizing effect of atmospheric nitrogen (N) deposition. These drivers are unlikely to operate independently, yet their combined effect on aboveground and belowground C storage remains largely unexplored. We sampled inside and outside 19 upland grazing exclosures, established for up to 80 years, across an N deposition gradient (5–24 kg N ha −1 yr −1 ) and found that herbivore removal increased aboveground plant C stocks, particularly in moss, shrubs and litter. Soil C storage increased with atmospheric N deposition, and this was moderated by the presence or absence of herbivores. In exclosures receiving above 11 kg N ha −1 year −1 , herbivore removal resulted in increased soil C stocks. This effect was typically greater for exclosures dominated by dwarf shrubs ( Calluna vulgaris ) than by grasses ( Molinia caerulea ). The same pattern was observed for ecosystem C storage. We used our data to predict C storage for a scenario of removing all large herbivores from UK heathlands. Predictions were made considering herbivore removal only (ignoring N deposition) and the combined effects of herbivore removal and current N deposition rates. Predictions including N deposition resulted in a smaller increase in UK heathland C storage than predictions using herbivore removal only. This finding was driven by the fact that the majority of UK heathlands receive low N deposition rates at which herbivore removal has little effect on C storage. Our findings demonstrate the crucial link between herbivory by large mammals and atmospheric N deposition, and this interaction needs to be considered in models of biogeochemical cycling.

Introduction of human pharmaceuticals from wastewater treatment plants into the aquatic environment: a rural perspective - Carolina Nebot; Raquel Falcon; Kenneth G. Boyd; Stuart W. Gibb (Environmental Science and Pollution Research, 2015)

Transposable elements as agents of rapid adaptation may explain the genetic paradox of invasive species - Jessica Stapley; Anna W. Santure; Stuart R. Dennis (Molecular Ecology, 2015)
Rapid adaptation of invasive species to novel habitats has puzzled evolutionary biologists for decades, especially as this often occurs in the face of limited genetic variability. Although some ecological traits common to invasive species have been identified, little is known about the possible genomic/genetic mechanisms that may underlie their success. A common scenario in many introductions is that small founder population sizes will often lead to reduced genetic diversity, but that invading populations experience large environmental perturbations, such as changes in habitat and environmental stress. Although sudden and intense stress is usually considered in a negative context, these perturbations may actually facilitate rapid adaptation by affecting genome structure, organization and function via interactions with transposable elements ( TE s), especially in populations with low genetic diversity. Stress‐induced changes in TE activity can alter gene action and can promote structural variation that may facilitate the rapid adaptation observed in new environments. We focus here on the adaptive potential of TE s in relation to invasive species and highlight their role as powerful mutational forces that can rapidly create genetic diversity. We hypothesize that activity of transposable elements can explain rapid adaptation despite low genetic variation (the genetic paradox of invasive species), and provide a framework under which this hypothesis can be tested using recently developed and emerging genomic technologies.

Productivity and fishing pressure drive variability in fish parasite assemblages of the Line Islands, equatorial Pacific - Chelsea L. Wood; Julia K. Baum; Sheila M. W. Reddy; Rowan Trebilco; Stuart A. Sandin; Brian J. Zgliczynski; Amy A. Briggs; Fiorenza Micheli (Ecology, 2015)
Variability in primary productivity and fishing pressure can shape the abundance, species composition, and diversity of marine life. Though parasites comprise nearly half of marine species, their responses to these important forces remain little explored. We quantified parasite assemblages at two spatial scales, across a gradient in productivity and fishing pressure that spans six coral islands of the Line Islands archipelago and within the largest Line Island, Kiritimati, which experiences a west‐to‐east gradient in fishing pressure and upwelling‐driven productivity. In the across‐islands data set, we found that increasing productivity was correlated with increased parasite abundance overall, but that the effects of productivity differed among parasite groups. Trophically transmitted parasites increased in abundance with increasing productivity, but directly transmitted parasites did not exhibit significant changes. This probably arises because productivity has stronger effects on the abundance of the planktonic crustaceans and herbivorous snails that serve as the intermediate hosts of trophically transmitted parasites than on the higher‐trophic level fishes that are the sole hosts of directly transmitted parasites. We also found that specialist parasites increased in response to increasing productivity, while generalists did not, possibly because specialist parasites tend to be more strongly limited by host availability than are generalist parasites. After the effect of productivity was controlled for, fishing was correlated with decreases in the abundance of trophically transmitted parasites, while directly transmitted parasites appeared to track host density; we observed increases in the abundance of parasites using hosts that experienced fishing‐driven compensatory increases in abundance. The within‐island data set confirmed these patterns for the combined effects of productivity and fishing on parasite abundance, suggesting that our conclusions are robust across a span of spatial scales. Overall, these results indicate that there are strong and variable effects of anthropogenic and natural drivers on parasite abundance and taxonomic richness. These effects are likely to be mediated by parasite traits, particularly by parasite transmission strategies.

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

A scenario-based risk framework for determining consequences of different failure modes of earth dams - Paul W. Cleary; Mahesh Prakash; Stuart Mead; Vincent Lemiale; Geoff K. Robinson; Fanghong Ye; Sida Ouyang; Xinming Tang (Natural Hazards, 2015)

Resolving issues with environmental impact assessment of marine renewable energy installations - Ilya M. D. Maclean; Richard Inger; David Benson; Cormac G. Booth; Clare B. Embling; W. James Grecian; Johanna J. Heymans; Kate E. Plummer; Michael Shackshaft; Carol E. Sparling; Ben Wilson; Lucy J. Wright; et al. (Frontiers in Marine Science, 2014)

Experimental evidence that invasive grasses use allelopathic biochemicals as a potential mechanism for invasion: chemical warfare in nature - Mitchell J. Greer; Gail W. T. Wilson; Karen R. Hickman; Stuart M. Wilson (Plant and Soil, 2014)

Novel molecular approach demonstrates that turbid river plumes reduce predation mortality on larval fish - Lucia B. Carreon‐Martinez; Kyle W. Wellband; Timothy B. Johnson; Stuart A. Ludsin; Daniel D. Heath (Molecular Ecology, 2014)
Turbidity associated with river plumes is known to affect the search ability of visual predators and thus can drive ‘top‐down’ impacts on prey populations in complex ecosystems; however, traditional quantification of predator–prey relationships (i.e. stomach content analysis) often fails with larval fish due to rapid digestion rates. Herein, we use novel molecular genetic methods to quantify larval yellow perch ( YP ) in predator stomachs in western Lake Erie to test the hypothesis that turbidity drives variation in larval predation. We characterize predator stomach content DNA to first identify YP DNA (single nucleotide polymorphism) and then quantify larval YP predation (microsatellite allele counting) in two river plumes differing in turbidity. Our results showed elevated larval YP predation in the less turbid river plume, consistent with a top‐down impact of turbidity on larval survival. Our analyses highlight novel ecological hypothesis testing using the power of innovative molecular genetic approaches.

Cassava Ivorian bacilliform virus is a member of the genus Anulavirus - Simon W. Scott; Stuart A. MacFarlane; Wendy J. McGavin; Denis Fargette (Archives of Virology, 2014)

Functional traits, land‐use change and the structure of present and future bird communities in tropical forests - Tim Newbold; Jörn P. W. Scharlemann; Stuart H. M. Butchart; Çağan H. Şekercioğlu; Lucas Joppa; Rob Alkemade; Drew W. Purves (Global Ecology and Biogeography, 2014)
Aim Habitat loss continues to cause loss of biodiversity. To quantify the effects of land‐use change on the diversity and composition of ecological communities – in terms of functional groups – we make modelled estimates of the impact of past and future (to 2050) land‐use change on the overall diversity and dietary guild structure of tropical forest bird communities. Location Tropical and subtropical forests (40° S to 40° N ). Methods Using a likelihood‐based model, we project the impact of land‐use intensity on the diversity and functional structure of tropical forest bird communities, including an estimation of uncertainty. To explore the extent to which predicted impacts are determined by the inherent sensitivity of communities because of the traits possessed by the species present, we quantify communities in terms of trait composition and explore relationships between trait composition and diversity/guild loss. Results We estimate that habitat loss has led to an average decrease of 4% in total abundance, but with marked differences across different guilds, leading to substantial changes in community composition: an 11.4% loss of frugivores, 7.8% loss of nectarivores and 7.3% loss of insectivores, and a 4.0% gain of other herbivores. Projected land‐use change is predicted to result in average future losses of 1% of total abundance, 1% of each of frugivores, nectarivores and insectivores, but no average change in the abundance of other herbivores. Past and future changes have varied substantially across the biome, owing to variation in land‐use change and in the initial trait composition of communities. Main conclusions We predict that marked changes in community structure have occurred in the past and will occur in the future, with disproportionate losses of frugivores, nectarivores and insectivores compared with other species; these species are known to provide important ecosystem services. In the past, South America has been particularly strongly affected, while Southeast Asia will experience the strongest impacts in the future.

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Mechanisms underpinning climatic impacts on natural populations: altered species interactions are more important than direct effects - Nancy Ockendon; David J. Baker; Jamie A. Carr; Elizabeth C. White; Rosamunde E. A. Almond; Tatsuya Amano; Esther Bertram; Richard B. Bradbury; Cassie Bradley; Stuart H. M. Butchart; Nathalie Doswald; Wendy Foden; et al. (Global Change Biology, 2014)
Shifts in species' distribution and abundance in response to climate change have been well documented, but the underpinning processes are still poorly understood. We present the results of a systematic literature review and meta‐analysis investigating the frequency and importance of different mechanisms by which climate has impacted natural populations. Most studies were from temperate latitudes of North America and Europe; almost half investigated bird populations. We found significantly greater support for indirect, biotic mechanisms than direct, abiotic mechanisms as mediators of the impact of climate on populations. In addition, biotic effects tended to have greater support than abiotic factors in studies of species from higher trophic levels. For primary consumers, the impact of climate was equally mediated by biotic and abiotic mechanisms, whereas for higher level consumers the mechanisms were most frequently biotic, such as predation or food availability. Biotic mechanisms were more frequently supported in studies that reported a directional trend in climate than in studies with no such climatic change, although sample sizes for this comparison were small. We call for more mechanistic studies of climate change impacts on populations, particularly in tropical systems.

Multilocation Corn Stover Harvest Effects on Crop Yields and Nutrient Removal - Douglas L. Karlen; Stuart J. Birrell; Jane M. F. Johnson; Shannon L. Osborne; Thomas E. Schumacher; Gary E. Varvel; Richard B. Ferguson; Jeff M. Novak; James R. Fredrick; John M. Baker; John A. Lamb; Paul R. Adler; et al. (BioEnergy Research, 2014)

The effects of 3,3′,4,4′-tetrabromobiphenyl on rats fed diets containing a constant level of copper and varying levels of molybdenum - Kadhim N. Salman; Mary A. Stuart; Jack Schmidt; T. Borges; Craig J. McClain; Farrel R. Robinson; Miao Li; Larry W. Robertson (Environmental Science and Pollution Research, 2014)

Optimizing Carbon Storage Within a Spatially Heterogeneous Upland Grassland Through Sheep Grazing Management - Stuart W. Smith; Charlotte Vandenberghe; Astley Hastings; David Johnson; Robin J. Pakeman; René van der Wal; Sarah J. Woodin (Ecosystems, 2014)

Mesozoic exhumation history and palaeolandscape of the Iberian Massif in eastern Galicia from apatite fission-track and (U+Th)/He data - R. W. Grobe; J. Alvarez-Marrón; U. A. Glasmacher; F. M. Stuart (International Journal of Earth Sciences, 2014)

Community‐based climate change adaptation strategies for integrated prawn–fish–rice farming in B angladesh to promote social–ecological resilience - Nesar Ahmed; Stuart W. Bunting; Sanzidur Rahman; Christopher J. Garforth (Reviews in Aquaculture, 2014)
Farming freshwater prawns with fish in rice fields is widespread in the coastal region of southwest B angladesh because of favourable resources and ecological conditions. This article provides an overview of an ecosystem‐based approach to integrated prawn–fish–rice farming in southwest B angladesh. The practice of prawn and fish farming in rice fields is a form of integrated aquaculture–agriculture, which provides a wide range of social, economic and environmental benefits. Integrated prawn–fish–rice farming plays an important role in the economy of B angladesh, earning foreign exchange and increasing food production. However, this unique farming system in coastal B angladesh is particularly vulnerable to climate change. We suggest that community‐based adaptation strategies must be developed to cope with the challenges. We propose that integrated prawn–fish–rice farming could be relocated from the coastal region to less vulnerable inland areas, but caution that this will require appropriate adaptation strategies and an enabling institutional environment.

Challenges in understanding the sources of bioaccumulated metals in biota inhabiting turbid river systems - Tom Cresswell; Ross E. W. Smith; Stuart L. Simpson (Environmental Science and Pollution Research, 2014)

A taxonomic comparison of local habitat niches of tropical trees - Claire A. Baldeck; Steven W. Kembel; Kyle E. Harms; Joseph B. Yavitt; Robert John; Benjamin L. Turner; George B. Chuyong; David Kenfack; Duncan W. Thomas; Sumedha Madawala; Nimal Gunatilleke; Savitri Gunatilleke; et al. (Oecologia, 2013)

Periprosthetic osteolysis after total hip replacement: molecular pathology and clinical management - Donald W. Howie; Susan D. Neale; David R. Haynes; Oksana T. Holubowycz; Margaret A. McGee; Lucian B. Solomon; Stuart A. Callary; Gerald J. Atkins; David M. Findlay (Inflammopharmacology, 2013)

Evaluation of the Oxoid Brilliance™ CRE Agar for the detection of carbapenemase-producing Enterobacteriaceae - J. Cohen Stuart; G. Voets; W. Rottier; S. Voskuil; J. Scharringa; K. Dijk; A. C. Fluit; M. Leverstein-Van Hall (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Challenges with tracing the fate and speciation of mine-derived metals in turbid river systems: implications for bioavailability - Tom Cresswell; Ross E. W. Smith; Dayanthi Nugegoda; Stuart L. Simpson (Environmental Science and Pollution Research, 2013)

Milling plant and soil material in plastic tubes over-estimates carbon and under-estimates nitrogen concentrations - Stuart W. Smith; A. H. Jean Robertson; Andrew A. Meharg; Robin J. Pakeman; David Johnson; Sarah J. Woodin; René van der Wal (Plant and Soil, 2013)

Differences in the antibiotic susceptibility of human Escherichia coli with poultry-associated and non-poultry-associated extended-spectrum beta-lactamases - T. N. Platteel; M. A. Leverstein-Van Hall; J. W. Cohen Stuart; G. M. Voets; M. P. Munckhof; J. Scharringa; N. Sande; A. C. Fluit; M. J. M. Bonten (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Steep clines within a highly permeable genome across a hybrid zone between two subspecies of the E uropean rabbit - Miguel Carneiro; Stuart J. E. Baird; Sandra Afonso; Esther Ramirez; Pedro Tarroso; Henrique Teotónio; Rafael Villafuerte; Michael W. Nachman; Nuno Ferrand (Molecular Ecology, 2013)
Maintenance of genetic distinction in the face of gene flow is an important aspect of the speciation process. Here, we provide a detailed spatial and genetic characterization of a hybrid zone between two subspecies of the European rabbit. We examined patterns of allele frequency change for 22 markers located on the autosomes, X ‐chromosome, Y ‐chromosome and mt DNA in 1078 individuals sampled across the hybrid zone. While some loci revealed extremely wide clines ( w ≥ 300 km) relative to an estimated dispersal of 1.95–4.22 km/generation, others showed abrupt transitions ( w ≈ 10 km), indicating localized genomic regions of strong selection against introgression. The subset of loci showing steep clines had largely coincident centers and stepped changes in allele frequency that did not co‐localize with any physical barrier or ecotone, suggesting that the rabbit hybrid zone is a tension zone. The steepest clines were for X ‐ and Y ‐chromosome markers. Our results are consistent with previous inference based on DNA sequence variation of individuals sampled in allopatry in suggesting that a large proportion of each genome has escaped the overall barrier to gene flow in the middle of the hybrid zone. These results imply an old history of hybridization and high effective gene flow and anticipate that isolation factors should often localize to small genomic regions.

Parental information use in the context of newborn bloodspot screening. An exploratory mixed methods study - Stuart G. Nicholls; K. W. Southern (Journal of Community Genetics, 2012)

Scent Chemicals of the Brushtail Possum, Trichosurus vulpecula - Stuart McLean; Noel W. Davies; Natasha L. Wiggins (Journal of Chemical Ecology, 2012)

Experimental litterfall manipulation drives large and rapid changes in soil carbon cycling in a wet tropical forest - Jonathan W. Leff; William R. Wieder; Philip G. Taylor; Alan R. Townsend; Diana R. Nemergut; A. Stuart Grandy; Cory C. Cleveland (Global Change Biology, 2012)
Global changes such as variations in plant net primary production are likely to drive shifts in leaf litterfall inputs to forest soils, but the effects of such changes on soil carbon ( C ) cycling and storage remain largely unknown, especially in C ‐rich tropical forest ecosystems. We initiated a leaf litterfall manipulation experiment in a tropical rain forest in C osta R ica to test the sensitivity of surface soil C pools and fluxes to different litter inputs. After only 2 years of treatment, doubling litterfall inputs increased surface soil C concentrations by 31%, removing litter from the forest floor drove a 26% reduction over the same time period, and these changes in soil C concentrations were associated with variations in dissolved organic matter fluxes, fine root biomass, microbial biomass, soil moisture, and nutrient fluxes. However, the litter manipulations had only small effects on soil organic C ( SOC ) chemistry, suggesting that changes in C cycling, nutrient cycling, and microbial processes in response to litter manipulation reflect shifts in the quantity rather than quality of SOC . The manipulation also affected soil CO 2 fluxes; the relative decline in CO 2 production was greater in the litter removal plots (−22%) than the increase in the litter addition plots (+15%). Our analysis showed that variations in CO 2 fluxes were strongly correlated with microbial biomass pools, soil C and nitrogen ( N ) pools, soil inorganic P fluxes, dissolved organic C fluxes, and fine root biomass. Together, our data suggest that shifts in leaf litter inputs in response to localized human disturbances and global environmental change could have rapid and important consequences for belowground C storage and fluxes in tropical rain forests, and highlight differences between tropical and temperate ecosystems, where belowground C cycling responses to changes in litterfall are generally slower and more subtle.

Genomic dissection and prioritizing of candidate genes of QTL for regulating spontaneous arthritis on chromosome 1 in mice deficient for interleukin-1 receptor antagonist - YANHONG CAO; JIFEI ZHANG; YAN JIAO; JIAN YAN; FENG JIAO; XIAOYUN LIU; ROBERT W. WILLIAMS; KAREN A. HASTY; JOHN M. STUART; WEIKUAN GU (Journal of Genetics, 2012)

Altered patterns of multiple recombinant events are associated with nondisjunction of chromosome 21 - Tiffany Renee Oliver; Stuart W. Tinker; Emily Graves Allen; Natasha Hollis; Adam E. Locke; Lora J. H. Bean; Reshmi Chowdhury; Ferdouse Begum; Mary Marazita; Vivian Cheung; Eleanor Feingold; Stephanie L. Sherman (Human Genetics, 2012)

Associations of exercise-induced hormone profiles and gains in strength and hypertrophy in a large cohort after weight training - Daniel W. D. West; Stuart M. Phillips (European Journal of Applied Physiology, 2012)

Rodenticide exposure in wood mouse and house mouse populations on farms and potential secondary risk to predators - David G. Tosh; Robbie A. McDonald; Stuart Bearhop; Neville R. Llewellyn; W. Ian Montgomery; Richard F. Shore (Ecotoxicology, 2012)

Altered Lung Motion is a Sensitive Indicator of Regional Lung Disease - Andreas Fouras; Beth J. Allison; Marcus J. Kitchen; Stephen Dubsky; Jayne Nguyen; Kerry Hourigan; Karen K. W. Siu; Rob A. Lewis; Megan J. Wallace; Stuart B. Hooper (Annals of Biomedical Engineering, 2012)

Erratum to: Activity of cortical and thalamic neurons during the slow (<1 Hz) rhythm in the mouse in vivo - Vincenzo Crunelli; Magor L. Lőrincz; Ying Bao; Adam C. Errington; Stuart W. Hughes (Pflügers Archiv - European Journal of Physiology, 2012)

The Effects of Soil Bacterial Community Structure on Decomposition in a Tropical Rain Forest - Jonathan W. Leff; Diana R. Nemergut; A. Stuart Grandy; Sean P. O’Neill; Kyle Wickings; Alan R. Townsend; Cory C. Cleveland (Ecosystems, 2012)

Temporal turnover in the composition of tropical tree communities: functional determinism and phylogenetic stochasticity - Nathan G. Swenson; James C. Stegen; Stuart J. Davies; David L. Erickson; Jimena Forero-Montaña; Allen H. Hurlbert; W. John Kress; Jill Thompson; María Uriarte; S. Joseph Wright; Jess K. Zimmerman (Ecology, 2012)
The degree to which turnover in biological communities is structured by deterministic or stochastic factors and the identities of influential deterministic factors are fundamental, yet unresolved, questions in ecology. Answers to these questions are particularly important for projecting the fate of forests with diverse disturbance histories worldwide. To uncover the processes governing turnover we use species‐level molecular phylogenies and functional trait data sets for two long‐term tropical forest plots with contrasting disturbance histories: one forest is older‐growth, and one was recently disturbed. Having both phylogenetic and functional information further allows us to parse out the deterministic influences of different ecological filters. With the use of null models we find that compositional turnover was random with respect to phylogeny on average, but highly nonrandom with respect to measured functional traits. Furthermore, as predicted by a deterministic assembly process, the older‐growth and disturbed forests were characterized by less than and greater than expected functional turnover, respectively. These results suggest that the abiotic environment, which changes due to succession in the disturbed forest, strongly governs the temporal dynamics of disturbed and undisturbed tropical forests. Predicting future changes in the composition of disturbed and undisturbed forests may therefore be tractable when using a functional‐trait‐based approach.

Activity of cortical and thalamic neurons during the slow (<1 Hz) rhythm in the mouse in vivo - Vincenzo Crunelli; Magor L. Lőrincz; Adam C. Errington; Stuart W. Hughes (Pflügers Archiv - European Journal of Physiology, 2012)

Localised control of an introduced predator: creating problems for the future? - Thomas W. Bodey; Stuart Bearhop; Robbie A. McDonald (Biological Invasions, 2011)

Integrated catchment management—interweaving social process and science knowledge - A Fenemor; C Phillips; W Allen; RG Young; G Harmsworth; B Bowden; L Basher; PA Gillespie; M Kilvington; R Davies‐Colley; J Dymond; A Cole; et al. (New Zealand Journal of Marine and Freshwater Research, 2011)
This paper provides an overview of the Motueka integrated catchment management (ICM) research programme. This research was based on the thesis that achieving ecosystem resilience at a catchment scale requires active measures to develop community resilience. We define a generic adaptive planning and action process, with associated knowledge management and stakeholder involvement processes, and illustrate those processes with observations from five research themes: (1) water allocation; (2) land use effects on water; (3) land and freshwater impacts on the coast; (4) integrative tools and processes for managing cumulative effects; and (5) building human capital and facilitating community action. Our research clearly illustrates the benefits for effective decision‐making of carrying out catchment scale science and management within collaborative processes which patiently develop trusting relationships. We conclude that coastal catchments should be managed as a holistic continuum from ridge tops to the sea and that some processes like floods or loss of community resilience have decadal consequences, which support the need for long‐term monitoring and investment.

A Method for Ensemble Wildland Fire Simulation - Mark A. Finney; Isaac C. Grenfell; Charles W. McHugh; Robert C. Seli; Diane Trethewey; Richard D. Stratton; Stuart Brittain (Environmental Modeling & Assessment, 2011)

NIR Spectroscopy Applications in the Development of a Compacted Multiparticulate System for Modified Release - Stuart L. Cantor; Stephen W. Hoag; Christopher D. Ellison; Mansoor A. Khan; Robbe C. Lyon (AAPS PharmSciTech, 2011)

The diet of an invasive nonnative predator, the feral ferret Mustela furo, and implications for the conservation of ground-nesting birds - Thomas W. Bodey; Stuart Bearhop; Robbie A. McDonald (European Journal of Wildlife Research, 2011)

Plumboselite, Pb3O2(SeO3), a new oxidation-zone mineral from Tsumeb, Namibia - Anthony R. Kampf; Stuart J. Mills; William W. Pinch (Mineralogy and Petrology, 2011)

Proposal for a revised taxonomy of the family Filoviridae: classification, names of taxa and viruses, and virus abbreviations - Jens H. Kuhn; Stephan Becker; Hideki Ebihara; Thomas W. Geisbert; Karl M. Johnson; Yoshihiro Kawaoka; W. Ian Lipkin; Ana I. Negredo; Sergey V. Netesov; Stuart T. Nichol; Gustavo Palacios; Clarence J. Peters; et al. (Archives of Virology, 2010)

Functional traits and the growth–mortality trade‐off in tropical trees - S. Joseph Wright; Kaoru Kitajima; Nathan J. B. Kraft; Peter B. Reich; Ian J. Wright; Daniel E. Bunker; Richard Condit; James W. Dalling; Stuart J. Davies; Sandra Díaz; Bettina M. J. Engelbrecht; Kyle E. Harms; et al. (Ecology, 2010)
A trade‐off between growth and mortality rates characterizes tree species in closed canopy forests. This trade‐off is maintained by inherent differences among species and spatial variation in light availability caused by canopy‐opening disturbances. We evaluated conditions under which the trade‐off is expressed and relationships with four key functional traits for 103 tree species from Barro Colorado Island, Panama. The trade‐off is strongest for saplings for growth rates of the fastest growing individuals and mortality rates of the slowest growing individuals ( r 2 = 0.69), intermediate for saplings for average growth rates and overall mortality rates ( r 2 = 0.46), and much weaker for large trees ( r 2 ≤ 0.10). This parallels likely levels of spatial variation in light availability, which is greatest for fast‐ vs. slow‐growing saplings and least for large trees with foliage in the forest canopy. Inherent attributes of species contributing to the trade‐off include abilities to disperse, acquire resources, grow rapidly, and tolerate shade and other stresses. There is growing interest in the possibility that functional traits might provide insight into such ecological differences and a growing consensus that seed mass (SM), leaf mass per area (LMA), wood density (WD), and maximum height ( H max ) are key traits among forest trees. Seed mass, LMA, WD, and H max are predicted to be small for light‐demanding species with rapid growth and mortality and large for shade‐tolerant species with slow growth and mortality. Six of these trait–demographic rate predictions were realized for saplings; however, with the exception of WD, the relationships were weak ( r 2 r 2 80% of the explained variation and, after WD was included, LMA and H max made insignificant contributions. Virtually the full range of values of SM, LMA, and H max occurred at all positions on the growth–mortality trade‐off. Although WD provides a promising start, a successful trait‐based ecology of tropical forest trees will require consideration of additional traits.

Nicotinic acetylcholine receptor genes on chromosome 15q25.1 are associated with nicotine and opioid dependence severity - Porat M. Erlich; Stuart N. Hoffman; Margaret Rukstalis; John J. Han; Xin Chu; W. H. Linda Kao; Glenn S. Gerhard; Walter F. Stewart; Joseph A. Boscarino (Human Genetics, 2010)

El Niño, grazers and fisheries interact to greatly elevate extinction risk for Galapagos marine species - GRAHAM J. EDGAR; STUART A. BANKS; MARGARITA BRANDT; RODRIGO H. BUSTAMANTE; ANGEL CHIRIBOGA; SYLVIA A. EARLE; LAUREN E. GARSKE; PETER W. GLYNN; JACK S. GROVE; SCOTT HENDERSON; CLEVE P. HICKMAN; KATHY A. MILLER; et al. (Global Change Biology, 2010)
Comparisons between historical and recent ecological datasets indicate that shallow reef habitats across the central Galapagos Archipelago underwent major transformation at the time of the severe 1982/1983 El Niño warming event. Heavily grazed reefs with crustose coralline algae (‘urchin barrens’) replaced former macroalgal and coral habitats, resulting in large local and regional declines in biodiversity. Following recent threat assessment workshops, a total of five mammals, six birds, five reptiles, six fishes, one echinoderm, seven corals, six brown algae and nine red algae reported from coastal environments in Galapagos are now recognized as globally threatened. The 2008 International Union for the Conservation of Nature (IUCN) Red List includes 43 of these species, while two additional species (Galapagos damsel Azurina eupalama and 24‐rayed sunstar Heliaster solaris ) not seen for > 25 years also fulfil IUCN threatened species criteria. Two endemic species (Galapagos stringweed Bifurcaria galapagensis and the damselfish A. eupalama ) are now regarded as probably extinct, while an additional six macroalgal species ( Dictyota galapagensis, Spatoglossum schmittii, Desmarestia tropica, Phycodrina elegans, Gracilaria skottsbergii and Galaxaura barbata ) and the seastar H. solaris are possibly extinct. The removal of large lobster and fish predators by artisanal fishing probably magnified impacts of the 1982/1983 El Niño through a cascade of indirect effects involving population expansion of grazing sea urchins. Marine protected areas with adequate enforcement are predicted to ameliorate but not eliminate ecosystem impacts caused by increasing thermal anomalies associated with El Niño and global climate change.

Wastewater‐fed aquaculture in the East Kolkata Wetlands, India: anachronism or archetype for resilient ecocultures? - Stuart W. Bunting; Jules Pretty; Peter Edwards (Reviews in Aquaculture, 2010)
Wastewater‐fed aquaculture is generally in decline. The 12 500 ha East Kolkata Wetlands (EKW) Ramsar site in peri‐urban Kolkata, India, is the only large‐scale formal system still operating and appears to demonstrate a high degree of resilience. This paper identifies aspects of wastewater‐fed aquaculture in the EKW that contribute to its sustained operation. The Driving Forces, Pressures, State, Impact, Response (DPSIR) framework was used to structure the assessment. Resilience within the EKW can be attributed to the scale of operation, adaptive production strategies that optimise resource utilisation while minimising risks, self‐organisation among stakeholders and timely legislation and institutional interventions to preserve the natural character of the wetlands. The introduction of externalising technologies, erosion of social capital and loss of traditional ecological knowledge threaten to undermine this resilience. Outcomes from this analysis should inform future management of the EKW to ensure that resilience is retained and enhanced.

The effect of weight loss on lameness in obese dogs with osteoarthritis - William G. Marshall; Herman A. W. Hazewinkel; Dermot Mullen; Geert De Meyer; Katrien Baert; Stuart Carmichael (Veterinary Research Communications, 2010)

Pattern orthogonalization via channel decorrelation by adaptive networks - Stuart D. Wick; Martin T. Wiechert; Rainer W. Friedrich; Hermann Riecke (Journal of Computational Neuroscience, 2010)

Sources of Elevated Chloride in Local Streams: Groundwater and Soils as Potential Reservoirs - Dustin W. Kincaid; Stuart E. G. Findlay (Water, Air, & Soil Pollution, 2009)

Papyriferic Acid, An Antifeedant Triterpene From Birch Trees, Inhibits Succinate Dehydrogenase From Liver Mitochondria - Stuart McLean; Stephen M. Richards; Siow-Leng Cover; Sue Brandon; Noel W. Davies; John P. Bryant; Thomas P. Clausen (Journal of Chemical Ecology, 2009)

Informed consent to tissue donation: policies and practice - Andrew Siegel; Martha W. Anderson; Tracy C. Schmidt; Stuart J. Youngner (Cell and Tissue Banking, 2009)

Evaluation of the genetic variability of orchid fleck virus by single-strand conformational polymorphism analysis and nucleotide sequencing of a fragment from the nucleocapsid gene - Karen Sumire Kubo; R. M. Stuart; J. Freitas-Astúa; R. Antonioli-Luizon; E. C. Locali-Fabris; H. D. Coletta-Filho; M. A. Machado; E. W. Kitajima (Archives of Virology, 2009)

Herbivore metabolism and stoichiometry each constrain herbivory at different organizational scales across ecosystems - Helmut Hillebrand; Elizabeth T. Borer; Matthew E. S. Bracken; Bradley J. Cardinale; Just Cebrian; Elsa E. Cleland; James J. Elser; Daniel S. Gruner; W. Stanley Harpole; Jacqueline T. Ngai; Stuart Sandin; Eric W. Seabloom; et al. (Ecology Letters, 2009)
Plant‐herbivore interactions mediate the trophic structure of ecosystems. We use a comprehensive data set extracted from the literature to test the relative explanatory power of two contrasting bodies of ecological theory, the metabolic theory of ecology (MTE) and ecological stoichiometry (ES), for per‐capita and population‐level rates of herbivory across ecosystems. We found that ambient temperature and herbivore body size (MTE) as well as stoichiometric mismatch (ES) both constrained herbivory, but at different scales of biological organization. Herbivore body size, which varied over 11 orders of magnitude, was the primary factor explaining variation in per‐capita rates of herbivory. Stoichiometric mismatch explained more variation in population‐level herbivory rates and also in per‐capita rates when we examined data from within functionally similar trophic groups (e.g. zooplankton). Thus, predictions from metabolic and stoichiometric theories offer complementary explanations for patterns of herbivory that operate at different scales of biological organization.

Nitrate removal in stream ecosystems measured by 15N addition experiments: Denitrification - Patrick J. Mulholland; Robert O. Hall; Daniel J. Sobota; Walter K. Dodds; Stuart E. G. Findlay; Nancy B. Grimm; Stephen K. Hamilton; William H. McDowell; Jonathan M. O'Brien; Jennifer L. Tank; Linda R. Ashkenas; Lee W. Cooper; et al. (Limnology and Oceanography, 2009)
We measured denitrification rates using a field 15 NO 3 − tracer‐addition approach in a large, cross‐site study of nitrate uptake in reference, agricultural, and suburban‐urban streams. We measured denitrification rates in 49 of 72 streams studied. Uptake length due to denitrification ( S Wden n) ranged from 89 m to 184 km (median of 9050 m) and there were no significant differences among regions or land‐use categories, likely because of the wide range of conditions within each region and land use. N 2 production rates far exceeded N 2 O production rates in all streams. The fraction of total NO 3 − removal from water due to denitrification ranged from 0.5% to 100% among streams (median of 16%), and was related to NH 4 + concentration and ecosystem respiration rate (ER). Multivariate approaches showed that the most important factors controlling S Wden were specific discharge (discharge / width) and NO 3 − concentration (positive effects), and ER and transient storage zones (negative effects). The relationship between areal denitrification rate ( U den ) and NO 3 − concentration indicated a partial saturation effect. A power function with an exponent of 0.5 described this relationship better than a Michaelis‐Menten equation. Although U den increased with increasing NO 3 − concentration, the efficiency of NO 3 − removal from water via denitrification declined, resulting in a smaller proportion of streamwater NO 3 − load removed over a given length of stream. Regional differences in stream denitrification rates were small relative to the proximate factors of NO 3 − concentration and ecosystem respiration rate, and land use was an important but indirect control on denitrification in streams, primarily via its effect on NO 3 − concentration.

Possible impacts of anthropogenic and natural aerosols on Australian climate: a review - Leon D. Rotstayn; Melita D. Keywood; Bruce W. Forgan; Albert J. Gabric; Ian E. Galbally; John L. Gras; Ashok K. Luhar; Grant H. McTainsh; Ross M. Mitchell; Stuart A. Young (International Journal of Climatology, 2009)
A review is presented of the aerosol–climate interaction with specific focus on the Australian region. The uncertainties associated with this interaction are much larger than those associated with greenhouse gases or other forcing agents, and are currently a major obstacle in climate‐change research. However, new research suggests that aerosol effects are of comparable importance to greenhouse gases as a driver of recent climate trends in the Southern Hemisphere, including Australia. A significant new result from climate modelling is that anthropogenic aerosol over Asia affects meridional temperature gradients and atmospheric circulation, and may have caused an increase in rainfall over north‐western Australia. Global ocean circulation provides another mechanism whereby aerosol changes in the Northern Hemisphere can affect climate in the Southern Hemisphere, suggesting an urgent need for further targeted studies using coupled ocean‐atmosphere global climate models. To better model climate variability and climate change in the Australian region, more research is needed into the sources of aerosol and their precursors, their atmospheric distributions and transformations, and how to incorporate these processes robustly in global climate models (GCMs). The following priorities are suggested for further research in Australia linking aerosol observations and modelling: natural aerosol over the Southern Ocean, tropical biomass‐burning aerosol in Indonesia and Australia, secondary organic aerosol (SOA) from volatile organic compounds (VOCs), wind‐blown dust and modulation of rainfall by anthropogenic aerosol. Copyright © 2008 Royal Meteorological Society

Bypassing cellular EGF receptor dependence through epithelial-to-mesenchymal-like transitions - Sharon Barr; Stuart Thomson; Elizabeth Buck; Suzanne Russo; Filippo Petti; Izabela Sujka-Kwok; Alexandra Eyzaguirre; Maryland Rosenfeld-Franklin; Neil W. Gibson; Mark Miglarese; David Epstein; Kenneth K. Iwata; et al. (Clinical & Experimental Metastasis, 2008)

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

A cross‐system synthesis of consumer and nutrient resource control on producer biomass - Daniel S. Gruner; Jennifer E. Smith; Eric W. Seabloom; Stuart A. Sandin; Jacqueline T. Ngai; Helmut Hillebrand; W. Stanley Harpole; James J. Elser; Elsa E. Cleland; Matthew E. S. Bracken; Elizabeth T. Borer; Benjamin M. Bolker (Ecology Letters, 2008)
Nutrient availability and herbivory control the biomass of primary producer communities to varying degrees across ecosystems. Ecological theory, individual experiments in many different systems, and system‐specific quantitative reviews have suggested that (i) bottom–up control is pervasive but top–down control is more influential in aquatic habitats relative to terrestrial systems and (ii) bottom–up and top–down forces are interdependent, with statistical interactions that synergize or dampen relative influences on producer biomass. We used simple dynamic models to review ecological mechanisms that generate independent vs. interactive responses of community‐level biomass. We calibrated these mechanistic predictions with the metrics of factorial meta‐analysis and tested their prevalence across freshwater, marine and terrestrial ecosystems with a comprehensive meta‐analysis of 191 factorial manipulations of herbivores and nutrients. Our analysis showed that producer community biomass increased with fertilization across all systems, although increases were greatest in freshwater habitats. Herbivore removal generally increased producer biomass in both freshwater and marine systems, but effects were inconsistent on land. With the exception of marine temperate rocky reef systems that showed positive synergism of nutrient enrichment and herbivore removal, experimental studies showed limited support for statistical interactions between nutrient and herbivory treatments on producer biomass. Top–down control of herbivores, compensatory behaviour of multiple herbivore guilds, spatial and temporal heterogeneity of interactions, and herbivore‐mediated nutrient recycling may lower the probability of consistent interactive effects on producer biomass. Continuing studies should expand the temporal and spatial scales of experiments, particularly in understudied terrestrial systems; broaden factorial designs to manipulate independently multiple producer resources (e.g. nitrogen, phosphorus, light), multiple herbivore taxa or guilds (e.g. vertebrates and invertebrates) and multiple trophic levels; and – in addition to measuring producer biomass – assess the responses of species diversity, community composition and nutrient status.

Landowner Willingness to Engage in Long-Term Timber Leases in West Virginia, USA - David W. McGill; Shawn T. Grushecky; Stuart Moss; Chad Pierskalla; Al Schuler (Small-scale Forestry, 2008)

A shift in the habitat use pattern of a lentic galaxiid fish: an acute behavioural response to an introduced predator - Rick D. Stuart-Smith; Robert W. G. White; Leon A. Barmuta (Environmental Biology of Fishes, 2008)

Horizontally integrated aquaculture development: Exploring consensus on constraints and opportunities with a stakeholder Delphi - Stuart W. Bunting (Aquaculture International, 2008)

Recovery of Aboveground Plant Biomass and Productivity After Fire in Mesic and Dry Black Spruce Forests of Interior Alaska - Michelle C. Mack; Kathleen K. Treseder; Kristen L. Manies; Jennifer W. Harden; Edward A. G. Schuur; Jason G. Vogel; James T. Randerson; F. Stuart Chapin (Ecosystems, 2008)

Ferrichrome utilization in a mesorhizobial population: microevolution of a three‐locus system - Timothy M. Carlton; John T. Sullivan; Gabriella S. Stuart; Karla Hutt; Iain L. Lamont; Clive W. Ronson (Environmental Microbiology, 2007)
Summary The ability to utilize the siderophore ferrichrome as an iron source was found to be a variable trait in a field population of mesorhizobia. To investigate the genetic basis of this variation, genes required for ferrichrome utilization ( fhu genes) were characterized in Mesorhizobium strain R88B, an Fhu + member of the population. Functional fhu genes were present at three loci. Two genes of the ferrichrome ABC transporter, fhuBD , were identified at an fhu1 locus downstream of the symbiosis island that was integrated at the phe‐tRNA gene. The fhuA gene encoding the ferrichrome outer membrane receptor was located in the fhu2 locus together with non‐functional fhuDB genes, while the fhuC gene encoding the ATPase required for ferrichrome transport was part of the fhu3 locus that included genes required to form a functional TonB complex. None of the fhu genes were present in the sequenced Mesorhizobium loti strain MAFF303099. Comparisons with MAFF303099 suggested that the fhu2 and fhu3 loci evolved through small‐scale ( fhu loci were coordinately regulated in response to iron availability. Within the mesorhizobial population, the ability to utilize ferrichrome was most strongly correlated with the presence of the fhuA gene. We hypothesize that the ferrichrome transport system evolved through cycles of gene acquisition and deletion, with the positive selection pressure of an iron‐poor or siderophore‐rich environment being offset by the negative pressure of the outer membrane receptor being a target for phage.

Interannual dynamics and phenology of bacterial communities in a eutrophic lake - Ashley Shade; Angela D. Kent; Stuart E. Jones; Ryan J. Newton; Eric W. Triplett; Katherine D. McMahon (Limnology and Oceanography, 2007)
We investigated patterns of intra‐ and interannual change in pelagic bacterial community composition (BCC, assessed using automated ribosomal intergenic spacer analysis) over six years in eutrophic Lake Mendota, Wisconsin. A regular phenology was repeated across years, implying that freshwater bacterial communities are more predictable in their dynamics than previously thought. Seasonal events, such as water column mixing and trends in water temperature, were most strongly related to BCC variation. Communities became progressively less similar across years between the months of May and September, when the lake was thermally stratified. Dissolved oxygen and nitrate + nitrite concentrations were highly correlated to BCC change within and across seasons. The relationship between BCC and seasonal drivers suggests that trajectories of community change observed over long time series will reflect large‐scale climate variation.

Sequencing EVC and EVC2 identifies mutations in two-thirds of Ellis–van Creveld syndrome patients - Stuart W. J. Tompson; Victor L. Ruiz-Perez; Helen J. Blair; Stephanie Barton; Victoria Navarro; Joanne L. Robson; Michael J. Wright; Judith A. Goodship (Human Genetics, 2006)

Measures of Nutrient Processes as Indicators of Stream Ecosystem Health - James W. Udy; Christine S. Fellows; Michael E. Bartkow; Stuart E. Bunn; Joanne E. Clapcott; Bronwyn D. Harch (Hydrobiologia, 2006)

Benthic Metabolism as an Indicator of Stream Ecosystem Health - Christine S. Fellows; Joanne E. Clapcott; James W. Udy; Stuart E. Bunn; Bronwyn D. Harch; Michael J. Smith; Peter M. Davies (Hydrobiologia, 2006)

A proteomic approach to the identification and characterisation of protein composition in wheat germ - Yunxian Mak; Daniel J. Skylas; Robert Willows; Angela Connolly; Stuart J. Cordwell; Colin W. Wrigley; Peter J. Sharp; Les Copeland (Functional & Integrative Genomics, 2006)

Nocturnal foraging by great skuas Stercorarius skua: implications for conservation of storm-petrel populations - Stephen C. Votier; Jonathan E. Crane; Stuart Bearhop; Ana de León; Claire A. McSorley; Eduardo Mínguez; Ian P. Mitchell; Matthew Parsons; Richard A. Phillips; Robert W. Furness (Journal of Ornithology, 2006)

Behavioral Responses of a Generalist Mammalian Folivore to the Physiological Constraints of a Chemically Defended Diet - Natasha L. Wiggins; Clare McArthur; Noel W. Davies; Stuart McLean (Journal of Chemical Ecology, 2006)

A comprehensive open reading frame phylogenetic analysis of isometric positive strand ssRNA plant viruses - G. W. Stuart; P. K. Moffett; R. F. Bozarth (Archives of Virology, 2006)

Endogenous production of endo-β-1,4-glucanase by decapod crustaceans - Stuart M. Linton; Peter Greenaway; David W. Towle (Journal of Comparative Physiology B, 2006)

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)

Lewis Ponds, a hybrid carbonate and volcanic-hosted polymetallic massive sulphide deposit, New South Wales, Australia - Michael W. Agnew; Ross R. Large; Stuart W. Bull (Mineralium Deposita, 2005)

Four days of citalopram increase suppression of cortisol secretion by prednisolone in healthy volunteers - Carmine M. Pariante; Andrew S. Papadopoulos; Lucia Poon; Anthony J. Cleare; Stuart A. Checkley; Judie English; Robert W. Kerwin; Stafford Lightman (Psychopharmacology, 2004)

Increasing turbidity significantly alters the diet of brown trout: a multi‐year longitudinal study - R. D. Stuart‐Smith; A. M. M. Richardson; R. W. G. White (Journal of Fish Biology, 2004)
The stomach contents of adult brown trout Salmo trutta from Lake Sorell, Tasmania, were analysed during 6 years of increasing turbidity to follow changes in the diet associated with dramatic changes in water clarity. Brown trout were sampled from 1996, when turbidity was 26 NTU, to 2001 when turbidity was 141 NTU. The mean relative volume of stomach contents decreased progressively to 2001, by which time it was only one sixth of that in 1996, and the mean diversity of prey in stomachs decreased from an average of more than six species per stomach in 1996 to one species in 2001. The species composition of stomach contents shifted from domination by the phreatoicid isopod Colubotelson sp., to the galaxiid fish Galaxias auratus and the amphipod Austrochiltonia australis , and then the cladoceran Daphnia carinata . To give an indication of diet changes over a typical yearly cycle in the current turbid state of the lake, a sample was taken from each season from December 2000 to September 2001. Two basic diets were found during the year; brown trout specialized on D. carinata in summer and autumn, and G. auratus in winter and spring. Mean diversity of prey was less than two species per stomach in all samples from 2000 to 2001, except for the sample from spring 2001 when it was 2·2 species per stomach, and the mean relative volume of stomach contents was more than three times greater in winter than any other season. The ways in which high turbidity may have influenced the changes in the brown trout diet observed since 1996 and the patterns evident during the seasons of 2000–2001 are discussed.

Conceptualizing irrigation project modernization through benchmarking and the rapid appraisal process - Charles M. Burt; Stuart W. Styles (Irrigation and Drainage, 2004)
Benchmarking is defined as a systematic process for achieving continued improvement in the irrigation sector through comparisons with relevant and achievable internal or external goals, norms, and standards. The three aspects of benchmarking are: evaluation of technical indicators (both internal and external); appraisal of the system processes; and an evaluation of service to users and their satisfaction with that service. The authors have incorporated all three components into a training program in which project staff learn the concepts of modernization and then evaluate their own project in a systematic rapid appraisal process (RAP). At the end of the training, internal and external indicators are developed for the project, and the local staff develop a priority list for modernization of the project. This paper will present the concepts of the RAP. Copyright © 2004 John Wiley & Sons, Ltd.

Soil databases and the problem of establishing regional biogeochemical trends - Karen W. Holmes; Dar A. Roberts; Stuart Sweeney; Izaya Numata; Eraldo Matricardi; Trent W. Biggs; Getulio Batista; Oliver A. Chadwick (Global Change Biology, 2004)
Regional and global environmental modeling depend on soil data for input layers or parameterization. However, randomly located observations, such as provided by agricultural databases, are not always representative of trends identified in field studies conducted under carefully controlled conditions. Many researchers lament the paucity of soil profile data in Amazônia, and suggest that given more data, regional studies would more closely approximate field research results. We assess the ability of a well‐populated regional database collected in the southwestern Brazilian Amazon to reproduce expected biogeochemical trends associated with forest clearing and pasture establishment, and explore the ramifications of relying on independently collected soil data for regional modeling. The Soteron database includes analyses of approximately 3000 soil cores collected for zoning purposes in the state of Rondônia. Pasture ages were determined from a time series of Landsat TM images classified using spectral mixture analysis. Although regional averages showed some of the temporal trends expected based on field study results (e.g. increase in pH following forest clearing), the trends were not statistically significant. Stratification by precipitation and other variables showed pasture age to be important but difficult to separate from other potential controls on soil conditions, mainly because of the reduced number of observations in each stratum. Using multiple regression, which permitted the inclusion of all potential explanatory factors and interactions, pasture age was shown to be a statistically significant predictor of soil conditions. However, the expected temporal sequence of changes documented by field chronosequence studies could not be reproduced. Properties dominated by large‐scale environmental gradients – pH, sum of base cations, aluminum saturation, and exchangeable calcium – were moderately well modeled, while those more strongly linked to dynamic spatially heterogeneous processes such as biological cycling and land management, particularly organic carbon and nitrogen, could not be modeled. Management‐induced soil changes occur at too fine a scale to be captured by most maps, and the relative changes are small compared with spatial heterogeneity caused by controls on soil development over large regions. Therefore, regardless of whether chronosequence‐derived models of biogeochemical response to land‐cover change are correct, the results of these models will not lead to spatially explicit maps that can be validated by regional reconnaissance, nor will they facilitate realistic predictions of the regional biogeochemical consequences of land‐cover change. The change from local to regional scale entails a change in the relative importance of processes controlling soil property behavior.

Mass flow sedimentology within the HYC Zn?Pb?Ag deposit, Northern Territory, Australia: evidence for syn-sedimentary ore genesis - Tim Ireland; Stuart W. Bull; Ross R. Large (Mineralium Deposita, 2004)

Jensenone: Biological Reactivity of a Marsupial Antifeedant from Eucalyptus - Stuart McLean; Sue Brandon; Noel W. Davies; William J. Foley; H. Konrad Muller (Journal of Chemical Ecology, 2004)

Complement - Dimitrios Mastellos; Dimitrios Morikis; Stuart N. Isaacs; M. Claire Holland; Cristoph W. Strey; John D. Lambris (Immunologic Research, 2003)

Glucuronuria in the Koala - Stuart McLean; Sue Brandon; Noel W. Davies; Rebecca Boyle; William J. Foley; Ben Moore; Georgia J. Pass (Journal of Chemical Ecology, 2003)

Assessing the diet of great skuas, Catharacta skua, using five different techniques - Stephen C. Votier; Stuart Bearhop; Aidan MacCormick; Norman Ratcliffe; Robert W. Furness (Polar Biology, 2003)

Expression, purification and characterization of cytochrome P450 Biol: a novel P450 involved in biotin synthesis in Bacillus subtilis - Amanda J. Green; Stuart L. Rivers; Myles Cheesman; Graeme A. Reid; Luca G. Quaroni; Iain D. G. Macdonald; Stephen K. Chapman; Andrew W. Munro (JBIC Journal of Biological Inorganic Chemistry, 2001)

Effects of land use and riparian flowpath on delivery of dissolved organic carbon to streams - Stuart Findlay; John M. Quinn; Christopher W. Hickey; Greg Burrell; Malcolm Downes (Limnology and Oceanography, 2001)
A set of near‐stream flowpaths in pasture, native forest and exotic pine plantations in New Zealand was sampled to describe differences in dissolved organic carbon (DOC). The quantity and bioavailability of DOC varied among flowpaths in different land uses, with higher concentrations of DOC in near‐stream flow paths than the parent groundwater emerging from the hillslope. Tiles incubated in these waters did not consistently yield higher bacterial growth rates than tiles incubated in groundwaters. DOC composition, measured as fluorescence and absorbance properties and extracellular enzyme fingerprints, differed significantly among land uses and position along flowpath. Differences in riparian vegetation can indirectly affect DOC by altering exposure to ultraviolet radiation. A 2‐h exposure of water from subsurface flowpaths to full sunlight caused marked changes in fluorescence characteristics of water from the pasture catchment but only small changes in water from the native forest catchment. There were up to fivefold differences in extracellular enzyme activities on tiles incubated in light‐exposed water for the native forest site, but not for the pasture site. Bacterial growth and respiration were higher on tiles incubated in native forest water exposed to sunlight, but there was no light effect on growth for tiles incubated in water from the pasture flowpath. These results indicate that riparian flowpaths will affect the quantity and character of DOC delivered to streams and ultraviolet exposure may, at least in some cases, alter DOC bioavailability.

Fuzzy structure and spatial dynamics of a declining woodland caribou population - James A. Schaefer; Alasdair M. Veitch; Fred H. Harrington; W. Kent Brown; John B. Theberge; Stuart N. Luttich (Oecologia, 2001)

Fate of the Dietary Terpene, P-Cymene, in the Male Koala - Rebecca Boyle; Stuart McLean; William J. Foley; Ben D. Moore; Noel W. Davies; Sue Brandon (Journal of Chemical Ecology, 2000)

Comparative Metabolism of Dietary Terpene, p-Cymene, in Generalist and Specialist Folivorous Marsupials - Rebecca Boyle; Stuart McLean; William J. Foley; Noel W. Davies (Journal of Chemical Ecology, 1999)

A new human prostate carcinoma cell line, 22Rv1 - R. Michael Sramkoski; Thomas G. Pretlow; Joseph M. Giaconia; Theresa P. Pretlow; Stuart Schwartz; Man-Sun Sy; Susan R. Marengo; Johng S. Rhim; Desheng Zhang; James W. Jacobberger (In Vitro Cellular & Developmental Biology - Animal, 1999)

The gap effect and express saccades in the auditory modality - R. Shafiq; Geoffrey W. Stuart; Jennifer Sandbach; Paul Maruff; Jon Currie (Experimental Brain Research, 1998)

Microbial enzymatic response to catchment‐scale variations in supply of dissolved organic carbon - Stuart Findlay; Christopher W. Hickey; John M. Quinn (New Zealand Journal of Marine and Freshwater Research, 1997)
A suite of exoenzyme activities was assayed in three New Zealand streams draining pasture, native forest, and a pine catchment. There were differences among catchments in activity of three of the five enzymes assayed (cello‐biohydrolase, N‐acetylglucosaminidase, and dihydroxylphenylalanine oxidation). A principal components analysis (PCA) demonstrates that patterns of enzyme activity can be used to separate the three stream types. An experimental addition of algal‐leachate, leaf‐litter leachate, and high dissolved organic carbon (DOC) water from a small seep also resulted in marked shifts in epilithic enzyme activities 1 day after DOC additions. Oxidative enzymes showed a particularly strong response to additions of humic DOC. As for the field samples, a PCA showed large differences among treatments indicating that exoenzyme patterns can be used to examine which DOC sources predominate in different streams. Application of this approach to describing differences among streams will require detailed seasonal sampling together with longer‐term experiments.

Twenty-Five Years of the Clean Water Act: How Clean Are Forest Practices? - George G. Ice; Gordon W. Stuart; Jack B. Waide; Lloyd C. Irland; Paul V. Ellefson (Journal of Forestry, 1997)

Do planktivorous fish structure the zooplankton communities in New Zealand lakes? - Erik Jeppesen; Torben Lauridsen; Stuart F. Mitchell; Carolyn W. Burns (New Zealand Journal of Marine and Freshwater Research, 1997)
We critically evaluate the prevailing view that the species composition of zooplankton communities in New Zealand lakes, and the abundance and size distribution of the zooplankton, are more commonly controlled by food and temperature than by predation. We conclude that predation may play a far more important role than was hitherto thought. This conclusion is based first on the seasonal zooplankton dynamics of several New Zealand lakes being similar to those in Danish lakes, in which fish predation has been shown to have major effects. Second, the indigenous planktivorous fish fauna in New Zealand lakes is dominated by larvae of benthic fish with a long breeding season (bullies) and other small potent zooplanktivores such as smelt and larvae of galaxiids. Patterns of diurnal vertical migration of zooplankton in several New Zealand lakes during summer are also consistent with it being a mechanism to escape from predation. Third, the dominant piscivorous fish (brown trout and rainbow trout) are only facultative piscivores and are therefore probably weaker predators on the planktivores than the more obligate piscivores in many north‐temperate lakes. Although various other explanations have been offered for the low ratio of zooplankton‐to‐phytoplankton biomass observed in New Zealand lakes, this phenomenon is equally consistent with high rates of predation. Re‐analyses of data from earlier investigations in Tomahawk Lagoon No. 2, provide evidence for a periodically high predation pressure on zooplankton during summer, which was further supported experimentally. We call for further investigation of top‐down control of zooplankton in New Zealand lakes. It is important not only for scientific understanding, but potentially also for lake management.

A Study of Iron Acquisition Mechanisms of Legionella pneumophila Grown in Chemostat Culture - Brian W. James; W. Stuart Mauchline; P. Julian Dennis; C. William Keevil (Current Microbiology, 1997)

Expression patterns of vascular-specific promoters RolC and Sh in transgenic potatoes and their use in engineering PLRV-resistant plants - Michael W. Graham; Stuart Craig; Peter M. Waterhouse* (Plant Molecular Biology, 1997)

The expression of redox proteins of denitrification inThiosphaera pantotropha grown with oxygen, nitrate, and nitrous oxide as electron acceptors - James W. B. Moir; David J. Richardson; Stuart J. Ferguson (Archives of Microbiology, 1995)

Avoidance behavior of juvenile striped bass,Morone saxatilis, subjected to simultaneous chlorine and elevated temperature conditions - Lenwood W. Hall; Stuart L. Margrey; Dennis T. Burton; William C. Graves (Archives of Environmental Contamination and Toxicology, 1983)

Isolation of parafluorophenylalanine-resistant mutants from HeLa cell cultures - Lester K. C. Yim; W. Dorsey Stuart (Biochemical Genetics, 1983)

Seasonal temperature and power plant chlorination effects on estuarine invertebrates - Stuart L. Margrey; Dennis T. Burton; Lenwood W. Hall (Archives of Environmental Contamination and Toxicology, 1981)

Rudimentary locus of Drosophila melanogaster: Partial purification of a carbamylphosphate synthase-aspartate transcarbamylase-dihydroorotase complex - Virginia M. Brothers; Stuart I. Tsubota; Susan E. Germeraad; James W. Fristrom (Biochemical Genetics, 1978)

Renal perfusion dynamics during preservation - Stephen W. Flax; John G. Webster; Stuart J. Updike; David T. Uehling (Annals of Biomedical Engineering, 1978)

Detection by a permutation test of periodicities in biological time series: Dependence of sensitivity on measurement precision - Stuart W. Smith; Robert H. Odell (Annals of Biomedical Engineering, 1976)

Humoral and secretory antibody responses to immunization with low and high dosage split influenza virus vaccine - F. L. Ruben; C. W. Potter; C. H. Stuart-Harris (Archives of Virology, 1975)

A permutation test for periodicities in short, noisy time series - Robert H. Odell; Stuart W. Smith; F. Eugene Yates (Annals of Biomedical Engineering, 1975)

Effects of suppressor mutations on nonallelic glucose 6-phosphate dehydrogenase mutants of Neurospora crassa - W. A. Scott; Stuart Brody (Biochemical Genetics, 1973)

Sun injury to cut potato seed - W. C. Edmundson; C. F. Clark; C. H. Metzger; J. C. Miller; Wm Stuart; L. C. Young (American Journal of Potato Research, 1939)

Review of literature - E. V. Hardenburg; W. M. Stuart; C. H. Metsger; W. B. Ward (American Journal of Potato Research, 1934)

Potato trends - W. Stuart (American Journal of Potato Research, 1933)

Review of recent literature - F. J. Stevenson; W. Stuart (American Journal of Potato Research, 1932)

The potato association of America loses a loyal member - W. Stuart (American Journal of Potato Research, 1932)

Review of recent literature - W. Stuart (American Journal of Potato Research, 1930)

Review of recent literature - W. Stuart (American Journal of Potato Research, 1930)

Notes - E. V. Hardenburg; J. T.; M. B. Chalker; F. M. Harrington; H. C. M; W. P. Kirkwood; A. G. Tolaas; W. Stuart (American Journal of Potato Research, 1930)

Review of recent literature - J. T.; W. Stuart; Donald Folsom (American Journal of Potato Research, 1930)

Review of recent literature - W. Stuart (American Journal of Potato Research, 1930)

Review of recent literature - W. Stuart (American Journal of Potato Research, 1930)

Review of recent literature - W. Stuart (American Journal of Potato Research, 1930)

Review of recent literature - E. V. Hardenburg; W. Stuart (American Journal of Potato Research, 1930)

Reviews of recent literature - W. Stuart (American Journal of Potato Research, 1929)

Review of recent literature - W. Stuart; W. S.; Wm. Stuart (American Journal of Potato Research, 1929)

Review of recent literature - W. Stuart (American Journal of Potato Research, 1928)

Notes - H. C. Moore; N. J. Thomas; C. W. Metzger; E. R. Bennett; C. W. Hungerford; W M. Stuart; W M. H. Martin; E. B. Tussing; H. H. Zimmerley; H. O. Werner (American Journal of Potato Research, 1928)

Review of recent literature - W. Stuart; W. S. (American Journal of Potato Research, 1928)

Review of recent literature - W. Stuart (American Journal of Potato Research, 1928)

Review of recent literature - H. M. Steece; Philip Brierley; W. Stuart; Philip Brierley; H. M. Steece; F. Weiss; T. McIntosh (American Journal of Potato Research, 1926)

Seed certification in british columbia - S. S. Phillips; E. A. Stokdyk; W. Stuart; H. C. Moore (American Journal of Potato Research, 1926)

What shall we believe? - W. Stuart (American Journal of Potato Research, 1926)

Notes on recent literature - W. Stuart; Walter M. Peacock; Philip Brierley (American Journal of Potato Research, 1926)

Seed potato number - W. Stuart (American Journal of Potato Research, 1926)

Notes on recent literature - W. Stuart; H. M. Steece; Walter M. Peacock; C. F. Clark (American Journal of Potato Research, 1926)

Kiwanians sponsor potato club work - P. R. Young; E. V. Hardenburg; B. E. Brown; Paul M. Williams; Daniel Dean; A. G. Waller; H. R. Talmage; H. C. Moore; J. G. Milward; W. Stuart; H. B. Stevens; R. W. Goss; et al. (American Journal of Potato Research, 1925)

Notes on recent literature - W. Stuart; Walter M. Peacock; E. V. Hardenburg; F. Weiss; Walter M. Peacock; C. O. Appleman (American Journal of Potato Research, 1925)

A large potato yield - James C. Knollin; W. Stuart (American Journal of Potato Research, 1924)

Notes on recent literature - C. F. Clark; W. Stuart (American Journal of Potato Research, 1924)

Announcements - W. Stuart (American Journal of Potato Research, 1924)

Potato notes - R. C. Zuckerman; W. Stuart; J. Tucker (American Journal of Potato Research, 1924)

Notes on recent literature - W. Stuart; C. F. Clark (American Journal of Potato Research, 1924)

Announcements - W. Stuart (American Journal of Potato Research, 1924)

Seed potato classification - W. Stuart (American Journal of Potato Research, 1924)

Notes on recent literature - W. Stuart; E. Artschwager (American Journal of Potato Research, 1924)

Announcements - W. Stuart; S. G. Peppin (American Journal of Potato Research, 1924)

Bankers finance maine potato grower’s exchange - W. Stuart (American Journal of Potato Research, 1924)

Notes on recent literature - Walter M. Peacock; W. Stuart (American Journal of Potato Research, 1924)

Potato notes - J. T. Rosa; C. Tice; A. E. Wilkinson; B. G. Southwick; E. A. Stokdyk; Ray D. Hews; E. L. Newdick; W. Stuart; H. C. Moore; H. O. Werner; J. F. Hockey; C. L. Bailey; et al. (American Journal of Potato Research, 1924)

Notes on recent literature - W. Stuart (American Journal of Potato Research, 1924)

Potato notes - C. W. Tice; J. T. Rosa; A. E. Wilkinson; E. A. Stokdyk; E. L. Newdick; Verdal T. Maxwell; C. F. Clark; W. Stuart; Charles A. Thompson; J. Gilbert Borton; Ellwood Douglass; Orley G. Bowen; et al. (American Journal of Potato Research, 1924)

Notes on recent literature - Walter M. Peacock; W. Stuart (American Journal of Potato Research, 1924)

Notes on recent literature - W. Stuart; W. M. Peacock (American Journal of Potato Research, 1924)

Potato notes - W. Stuart; W. H. Martin; Glenn Carter; C. R. Inglee; H. H. Zimmerly (American Journal of Potato Research, 1924)

Potato notes - C. Tice; W. C. Edmundson; W. Stuart; Seymour Bridge; Glen Carter; A. G. Allen; Daniel Dean; H. H. Zimmerly; J. O. Milward (American Journal of Potato Research, 1924)

Announcement - W. Stuart (American Journal of Potato Research, 1924)

What size of seed piece or set should we plant? - W. Stuart (American Journal of Potato Research, 1924)

Notes on recent literature - W. Stuart (American Journal of Potato Research, 1924)

Potato notes - W. C. Edmundson; W. Stuart; J. C. Crissey; E. V. Hardenburg; W. Stuart (American Journal of Potato Research, 1924)

A forward look - W. Stuart (American Journal of Potato Research, 1924)

Notes on recent literature - C. F. Clark; W. Stuart; W. P. Hartman; W. D. Hurd; W. M. Peacock; H. M. Steece (American Journal of Potato Research, 1924)

Notes on recent literature - W. Stuart; W. M. Peacock; W. S. Baird; W. Saxby Blair; R. H. Helmer; W. H. Hicks; W. R. Leslie; B. F. Lutman; H. H. Mann; S. D. Nagpurkar; G. S. Kulkarni; R. S. Kasargode; et al. (American Journal of Potato Research, 1924)

Suggestions - W. Stuart (American Journal of Potato Research, 1924)

Notes on recent literature - W. Stuart (American Journal of Potato Research, 1924)

Seed certification notes - M. F. Barrus; W. Stuart; A. W. Tompkins; A. H. Gilbert; J. G. Milward (American Journal of Potato Research, 1924)

Report of Cincinnati meeting - W. Stuart (American Journal of Potato Research, 1924)

Potato association of america—what it stands for and its needs - W. Stuart (American Journal of Potato Research, 1923)

Notes on recent literatur - W. Stuart; W. H. M.; C. F. Clark; W. Stuart; Donald Folsom (American Journal of Potato Research, 1923)

Preliminary seed certification notes - E. R. Dykeman; C. H. Hadley; W. A. McCubbin; Harold L. Bailey; O Butler; M. F. Barrus; R. F. Payne; N. W. Glimes; H. O. Werner; W. Stuart; Donald Folsom; W. H. M. (American Journal of Potato Research, 1923)

Summary of yields - H. H. Zimmerly; W. Stuart (American Journal of Potato Research, 1923)

Potato notes - Lou D. Sweet; W. Stuart; E. V. Hardenburg; H. C. Moore; W. H. Martin (American Journal of Potato Research, 1923)

Notes on recent literature - C. F. Clark; W. Stuart (American Journal of Potato Research, 1923)

Annual meeting - W. M. Stuart (American Journal of Potato Research, 1923)

Foreword - W. M. Stuart (American Journal of Potato Research, 1923)